Fluoropolyether-based curable composition, cured product, and electrical / electronic component

By using highly compatible fluorine-containing organohydrogen silane compounds and fillers in fluoropolyether-based cured products, the low durability and compatibility of fluoropolyether-based cured products in hydrofluoric acid and lithium-ion batteries has been solved. The problem of high mechanical physical properties and good mold release properties are achieved.

CN119173582APending Publication Date: 2024-12-20SHIN ETSU CHEMICAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380038253.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-27
Filing Date
2023-04-28
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing fluoropolyether-based cured substances have low durability in hydrofluoric acid and lithium-ion battery electrolytes, and the synthesis of fluorine-containing organohydrogen siloxanes leads to compatibility problems and uncured parts, which affects the manufacturing process.

Method used

The fluorine-containing organohydrogen silane compound having more than three hydrogen silyl groups is combined with a perfluoropolyether group as a curing agent, and the polyimide resin powder and carbon black powder are used as fillers to increase the filling amount by pulverizing treatment. , a fluoropolyether-based curable composition with high compatibility, acid resistance and good mold release properties is formed.

Benefits of technology

It realizes durability to hydrofluoric acid and lithium-ion battery electrolyte, avoids uncured part dispersion, improves mechanical physical properties and mold release properties, and has heat resistance and resistance comparable to traditional fluoropolyether-based cured substances. Chemical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005116800810000041
    Figure BDA0005116800810000041
  • Figure BDA0005116800810000042
    Figure BDA0005116800810000042
  • Figure BDA0005116800810000051
    Figure BDA0005116800810000051
Patent Text Reader

Abstract

Containing (A) a perfluoropolyether compound having two or more alkenyl groups in one molecule, (B) a fluorine-containing organohydrosilane compound having two or more hydrosilyl groups and having a specific structure, (C) a platinum group metal catalyst, and (D) According to the present invention, a specific amount of a fluoropolyether-based curable composition containing at least one filler selected from among organic resin powders and carbon black powders can provide durability with respect to hydrofluoric acid and electrolyte solutions for lithium ion batteries, good mechanical and physical properties, and no uncured sites due to low compatibility between constituent components. The fluoropolyether-based curable composition is a cured product having good mold release properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a fluoropolyether-based curable composition containing at least one filler selected from organic resin powders such as polyimide resin powders and carbon black powders, which provides a cured product having durability against hydrofluoric acid and an electrolyte for lithium ion batteries, a cured product of the composition, and an electric or electronic component having the cured product. Background Art

[0002] Fluoropolyether curing compositions utilizing the addition reaction of alkenyl and hydrosilyl groups are well known. For example, as curing compositions, compositions comprising fluoropolyether compounds (hereinafter also described as "base oils") having two or more alkenyl groups in one molecule and having a perfluoropolyether structure in the main chain, compositions of fluorinated organohydrogensiloxanes and platinum group metal compounds having two or more hydrogen atoms directly bonded to silicon atoms in one molecule are proposed (Patent Document 1: Japanese Patent Laid-Open No. 8-199070 Gazette, Patent Document 2: Japanese Patent Laid-Open No. 2011-201940 Gazette). In addition, compositions having self-adhesive properties by adding organopolysiloxanes having hydrosilyl groups and epoxy groups and / or trialkoxysilyl groups to the composition are proposed (Patent Document 3: Japanese Patent Laid-Open No. 9-95615 Gazette, Patent Document 4: Japanese Patent Laid-Open No. 2011-219692 Gazette). The composition can be cured by heating for a short time, and the obtained cured product (fluoropolyether-based cured product) has excellent solvent resistance, chemical resistance, heat resistance, low temperature characteristics, low moisture permeability, electrical properties, etc., and has therefore been used in various industrial fields requiring these characteristics.

[0003] A fluoropolyether curable composition containing a fluorinated organohydrogensiloxane having two or more hydrogen atoms directly bonded to a silicon atom in one molecule contains a siloxane bond that is unstable to acid, and cannot fully exert its performance in applications requiring a high level of acid resistance. In particular, it has low durability to hydrofluoric acid and is not suitable for applications such as parts for semiconductor manufacturing equipment. In response to this, it has been proposed to improve the acid resistance of a fluoropolyether cured product by replacing the fluorinated organohydrogensiloxane with a fluorinated organohydrogensilane compound that does not contain a siloxane bond and has two or more hydrogen atoms directly bonded to a silicon atom in one molecule (Patent Document 5: Japanese Patent Publication No. 2002-012769).

[0004] However, in most cases, the curable composition contains a large amount of silica as a reinforcing filler. Silica shows high reactivity to hydrofluoric acid, so when the excellent mechanical and physical properties of the cured product, especially hardness and tensile strength, are emphasized in addition to acid resistance, it is necessary to use other fillers that can show the reinforcing effect of the cured product based on the countermeasure of not containing silica or reducing the content of silica.

[0005] In addition, the above-mentioned fluorinated organic hydrogen silane compound has a tendency to increase the proportion of the overall molecule of the non-fluorinated organic structure. This is mainly due to the synthesis of the fluorinated organic hydrogen silane compound. In this case, the short-chain perfluoroalkylene lacks compatibility with the base oil. Due to these tendencies, if a fluorinated organic hydrogen silane compound is added to a fluoropolyether-based curing composition, the fluoropolyether-based curing composition sometimes becomes turbid and the viscosity increases. In addition, on the surface of the fluoropolyether-based cured product obtained from the fluoropolyether-based curing composition, oily uncured parts are sometimes also scattered. Due to the spreading of the uncured parts, the demoulding property of the fluoropolyether-based cured product is often impaired. In the manufacturing process of an article containing the cured product, an unfavorable situation occurs in which the cured product can no longer be smoothly manufactured without being peeled off from the components in the manufacturing equipment, so it is not preferred.

[0006] Due to the increasing concern about environmental issues in recent years, the development of products using lithium-ion batteries has been actively carried out around the world. However, it is known that the fluoropolyether-based curable composition containing a fluorinated organohydrogensiloxane having two or more hydrogen atoms directly bonded to silicon atoms in one molecule and its cured product have low durability for electrolytes for lithium-ion batteries, and are difficult to use for this purpose. In addition, for fluoropolyether-based curable compositions and cured products containing a fluorinated organohydrogensilane compound that does not contain a siloxane bond and has two or more hydrogen atoms directly bonded to silicon atoms in one molecule instead of the fluorinated organohydrogensiloxane, there is no knowledge about the durability for electrolytes for lithium-ion batteries, and it is unclear whether they can be used for this purpose.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 8-199070

[0010] Patent Document 2: Japanese Patent Application Publication No. 2011-201940

[0011] Patent Document 3: Japanese Patent Application Laid-Open No. 9-95615

[0012] Patent Document 4: Japanese Patent Application Publication No. 2011-219692

[0013] Patent Document 5: Japanese Patent Application Publication No. 2002-012769 Summary of the invention

[0014] Problems to be solved by the invention

[0015] The present invention has been made in view of the above-mentioned actual situation, and an object of the present invention is to provide a fluoropolyether-based curable composition that has durability against hydrofluoric acid and an electrolyte for lithium ion batteries, has excellent mechanical properties, has no uncured portions due to low compatibility between constituent components, and provides a cured product having excellent mold release properties, a cured product of the composition, and an electric or electronic component having the cured product.

[0016] Means for solving problems

[0017] The inventors have conducted in-depth research to solve the above-mentioned problems, and the results show that as a curing agent for a fluoropolyether-based curable composition, when a fluorinated organic hydrogen silane compound obtained by introducing a compound having a monovalent perfluoropolyether group and an alkenyl group into an organic hydrogen silane compound having more than 3 hydrosilyl groups of a specified structure is used, it shows high compatibility with a perfluoropolyether compound having an alkenyl group as a base oil. It is found that the cured product obtained by curing the fluoropolyether-based curable composition to which the fluorinated organic hydrogen silane compound is added shows durability against hydrofluoric acid and an electrolyte for lithium ion batteries, and there is no uncured part on the surface, and it has good demoulding properties. In addition, it is found that, as a filler, by using at least one filler selected from an organic resin powder such as a polyimide resin powder and a carbon black powder, the mechanical and physical properties of the cured product can be improved without damaging the acid resistance. In addition, it was found that commercially available organic resin powders such as polyimide resin powders generally have an average particle size of 10 μm or more, and that by pulverizing the organic resin powders such as polyimide resin powders, the average particle size is reduced to several μm or less. When the pulverized organic resin powders such as polyimide resin powders are blended into a fluoropolyether-based curable composition, the amount that can be filled is increased compared to organic resin powders such as polyimide resin powders having an average particle size of 10 μm or more, thereby further reinforcing the cured product obtained from the fluoropolyether-based curable composition, thereby completing the present invention.

[0018] Therefore, the present invention provides the following fluoropolyether-based curable composition, a cured product obtained from the curable composition, and an electric or electronic component including the cured product.

[0019] [1] A fluoropolyether curable composition comprising:

[0020] (A) a perfluoropolyether compound having two or more alkenyl groups in one molecule: 100 parts by mass,

[0021] (B) a fluorinated organohydrogensilane compound represented by the following general formula (1) and having two or more hydrosilyl groups, in an amount such that the number of hydrogen atoms bonded to silicon atoms in the component (B) is 0.1 to 2.5 mol per 1 mol of alkenyl groups in the component (A);

[0022] [Chemistry 1]

[0023]

[0024] (In the formula, Rf is a monovalent perfluoropolyether group, A is a divalent organic group having 1 to 20 carbon atoms which may contain at least one selected from an oxygen atom, a nitrogen atom and a silicon atom, R is independently a monovalent hydrocarbon group having 1 to 6 carbon atoms, x is an integer of 1 to 3, B is independently a monovalent organic group having one or more diorganohydrogensilyl groups and forming a silylene structure with the connected silicon atom, when x is 1, B has two or more diorganohydrogensilyl groups, and y is 1 or 2.)

[0025] (C) platinum group metal catalyst: 0.1 to 2000 ppm in terms of platinum group metal atoms relative to the mass of component (A); and

[0026] (D) at least one filler selected from organic resin powder and carbon black powder: 0.1 to 200 parts by mass.

[0027] [2] The fluoropolyether curable composition according to [1], wherein the component (A) is a perfluoropolyether compound represented by the following general formula (2):

[0028] [Chemistry 2]

[0029]

[0030] [Where A 1 are independently a divalent organic group having 1 to 20 carbon atoms which may contain at least one selected from an oxygen atom, a nitrogen atom and a silicon atom, 1 is a carbon atom or a silicon atom, X is independently a hydrogen atom, a methyl group or an alkenyl group having 2 to 8 carbon atoms, wherein at least two Xs are alkenyl groups having 2 to 8 carbon atoms, and when Xs are hydrogen atoms, the bonded B 1 is a carbon atom. 1 is a divalent perfluoropolyether group.]

[0031] [3] The fluoropolyether curable composition according to [1] or [2], wherein in the component (B), Rf in the general formula (1) is a group represented by the following general formula (5):

[0032] [Chemistry 3]

[0033]

[0034] (In the formula, D is a fluorine atom or a perfluorooxyalkyl group having 1 to 6 carbon atoms, a, b, c and d are each independently an integer of 0 to 100, 2≤a+b+c+d≤100, e is an integer of 1 to 3, and each repeating unit shown in () may be randomly bonded, and each of these units may be linear or branched.)

[0035] [4] The fluoropolyether curable composition according to any one of [1] to [3], wherein in the component (B), A in the general formula (1) is selected from an alkylene group having 1 to 12 carbon atoms, an alkylene group containing an arylene group having 6 to 8 carbon atoms, a divalent group in which alkylene groups are bonded to each other via a diorganosilylene group, a divalent group in which an alkylene group and an arylene group are bonded to each other via a diorganosilylene group, and a divalent group in which these groups further have at least one selected from an ether bond oxygen atom, a secondary amino group, a tertiary amino group and an amide bond.

[0036] [5] The fluoropolyether curable composition according to any one of [1] to [4], wherein in the component (B), A in the general formula (1) is any one of the groups represented by the following general formulas (6) to (9).

[0037] [Chemistry 4]

[0038]

[0039] (Where X 0 is a hydrogen atom, a methyl group or an ethyl group, X 1 are independently a hydrogen atom, a fluorine atom, a methyl group, an ethyl group or a trifluoromethyl group, X 2 is a hydrogen atom, a methyl group, an ethyl group, an isopropyl group or a phenyl group, R' is independently a methyl group or an ethyl group, f is an integer of 1 to 6, and t is 0 or 1. In addition, the bonding end with * indicates bonding to the Si atom in the general formula (1), and the bonding end without a mark indicates bonding to Rf.)

[0040] [6] The fluoropolyether curable composition according to any one of [1] to [5], wherein in the component (B), R in the general formula (1) is any one of a methyl group, an ethyl group, an isopropyl group, a tert-butyl group, and a phenyl group.

[0041] [7] The fluoropolyether curable composition according to any one of [1] to [6], wherein in component (B), two or more silylene structures are continuous in the molecular chain between Rf in the general formula (1) and the diorganohydrogensilyl group in B.

[0042] [8] The fluoropolyether curable composition according to any one of [1] to [7], wherein in the component (B), B in the general formula (1) is a group represented by the following general formula (10):

[0043] [Chemistry 5]

[0044]

[0045] [wherein, p is an integer of 1 to 6, q is an integer of 0 to 6, r is an integer of 1 to 3, R is the same as above, and E is a hydrogen atom or a

[0046] [Chemistry 6]

[0047]

[0048] A group represented by (wherein R is the same as above, p' is an integer of 1 to 6, and q' is an integer of 0 to 6.) (However, when E is a hydrogen atom, r is 1.) The repeating units shown in () with the above p, q or p', q' may be randomly bonded.]

[0049] [9] The fluoropolyether curable composition according to any one of [1] to [8], wherein the component (B) is selected from a fluorinated organohydrogensilane compound represented by the following formula:

[0050] [Chemistry 7]

[0051]

[0052] [Chemistry 8]

[0053]

[0054] [Chemistry 9]

[0055]

[0056] [Chemistry 10]

[0057]

[0058] [Chemistry 11]

[0059]

[0060] [Chemistry 12]

[0061]

[0062] [Chemistry 13]

[0063]

[0064] (In the formula, b' is an integer from 2 to 100, c'" and d" are each an integer from 1 to 99, c'"+d"=2 to 100, ca' is an integer from 1 to 99, Me is a methyl group, Et is an ethyl group, Ph is a phenyl group, and the repeating units shown in () with c'" and d" may be randomly bonded.).

[0065]

[10] The fluoropolyether curable composition according to any one of [1] to [9], wherein the average particle size of the component (D) is 0.001 to 100 μm.

[0066]

[11] The fluoropolyether curable composition according to any one of [1] to

[10] , wherein the component (D) is a polyimide resin powder and / or a carbon black powder.

[0067]

[12] The fluoropolyether curable composition according to any one of [1] to [9], wherein the component (D) is a pulverized organic resin powder.

[0068]

[13] The fluoropolyether curable composition according to

[12] , wherein the average particle size of the component (D) is 0.001 to 5 μm.

[0069]

[14] The fluoropolyether curable composition according to

[12] or

[13] , wherein the component (D) is a polyimide resin powder.

[0070]

[15] The fluoropolyether curable composition according to any one of

[12] to

[14] , wherein the amount of the component (D) is 10 to 200 parts by mass based on 100 parts by mass of the component (A).

[0071]

[16] A cured product obtained from the fluoropolyether curable composition according to any one of [1] to

[15] .

[0072]

[17] An electric or electronic component comprising the cured product according to

[16] .

[0073]

[18] The electric or electronic component according to

[17] , wherein the cured product is a gasket, a filler, a protective seal, or a coating layer.

[0074]

[19] The electrical and electronic component according to

[17] or

[18] , which is used in automobiles, chemical equipment, semiconductor manufacturing lines, analytical physical and chemical equipment, residential environments, communication machinery, communication equipment, aircraft, railway vehicles, portable devices, power storage devices, robots, or lithium-ion batteries.

[0075] Effects of the Invention

[0076] The fluoropolyether curable composition of the present invention contains a fluorine-containing organohydrogensilane compound of a specific structure that shows high compatibility with the above-mentioned (A) component as the base oil, so that the fluoropolyether curable composition does not cause white turbidity and viscosity increase. In addition, by curing the composition, a fluoropolyether cured product having durability against hydrofluoric acid and an electrolyte for lithium ion batteries and without spreading of oily uncured parts can be obtained. Furthermore, as a filler, by using at least one filler selected from organic resin powders such as polyimide resin powders and carbon black powders, the mechanical properties of the cured product can be improved without impairing acid resistance. Furthermore, by subjecting the organic resin powder to a pulverization treatment, the amount that can be filled in the fluoropolyether curable composition is increased, and the mechanical properties can also be improved. The fluoropolyether curable composition has excellent heat resistance, chemical resistance, and solvent resistance comparable to those of the fluoropolyether cured products obtained from the fluoropolyether curable compositions described in Patent Documents 1 to 5, and has good mechanical properties. DETAILED DESCRIPTION

[0077] The present invention is described in more detail below.

[0078] [(A) ingredient]

[0079] The perfluoropolyether compound of the component (A) used in the fluoropolyether curable composition of the present invention has at least two alkenyl groups in one molecule, and is preferably a compound having a divalent perfluoropolyether structure in the main chain as represented by the general formula (2) described below, and functions as a main agent (base oil) in the fluoropolyether curable composition of the present invention.

[0080] In the present invention, the degree of polymerization (or molecular weight) of the polyfluoro compound, which reflects the number of repetitions of the perfluorooxyalkylene unit constituting the perfluoropolyether structure of the main chain, can be obtained, for example, as the number average degree of polymerization (or number average molecular weight) in terms of polystyrene in gel permeation chromatography (GPC) analysis using a fluorine-based solvent as an elution solvent. In addition, the number average degree of polymerization (or number average molecular weight) of the perfluoropolyether compound described later can also be obtained by 19 F-NMR calculation (the same below).

[0081] The component (A) is preferably a perfluoropolyether compound having a structure represented by the following general formula (2).

[0082] [Chemistry 14]

[0083]

[0084] [Where A 1 are independently a divalent organic group having 1 to 20 carbon atoms which may contain at least one selected from an oxygen atom, a nitrogen atom and a silicon atom, 1is a carbon atom or a silicon atom, X is independently a hydrogen atom, a methyl group or an alkenyl group having 2 to 8 carbon atoms, but at least two X are alkenyl groups having 2 to 8 carbon atoms, and when X is a hydrogen atom, the bonded B 1 is a carbon atom. 1 is a divalent perfluoropolyether group.]

[0085] In the above general formula (2), A 1 A is independently a divalent organic group having 1 to 20 carbon atoms which may contain at least one selected from an oxygen atom, a nitrogen atom and a silicon atom, preferably a divalent hydrocarbon group having 1 to 20 carbon atoms which may contain at least one selected from an oxygen atom, a nitrogen atom and a silicon atom. 1 , preferably selected from -(CH2) f -*, -OCH2-*, -(CH2) f OCH2-*、-(CH2) f -NX 2 -CO-*, -(CH2) f -O-CO-*, or any of the following general formulas (3) and (4). 1 Bonding, unmarked bonding ends indicate bonding with B 1 Bonding.

[0086] [Chemistry 15]

[0087]

[0088] (Where X 1 are independently a hydrogen atom, a fluorine atom, a methyl group, an ethyl group or a trifluoromethyl group, X 2 is a hydrogen atom, a methyl group, an ethyl group, an isopropyl group or a phenyl group, and f is an integer from 1 to 6.)

[0089] As A 1 For example, -CH2-*, -CH2CH2CH2-*, -OCH2-*, -CH2OCH2-*, -(CH2)2OCH2-*, -(CH2)3OCH2-*, -CH2-NH-CO-*, -CH2-N(CH3)-CO-*, -CH2CH2-NH-CO-*, -(CH2)3-NH-CO-*, -(CH2)3-N(CH3)-CO-*, -(CH2)3-N(CH2CH3)-CO-*, -(CH2)3-N(CH(CH3)2)-CO-*, -(CH2)3-O-CO-*, and groups represented by the following general formulae (3A), (3B), (3C), (3D), (4A), (4B) and (4C), among which groups represented by general formula (3A) or (4A) are preferred. In addition, the bonding end with * indicates the bonding end with Rf1 Bonding, unmarked bonding ends indicate bonding with B 1 In the formula, Me is a methyl group and Et is an ethyl group.

[0090] [Chemistry 16]

[0091]

[0092] In the above general formula (2), B 1 A carbon atom or a silicon atom.

[0093] In addition, X is independently a hydrogen atom, a methyl group or an alkenyl group having 2 to 8 carbon atoms, but at least two X groups are alkenyl groups having 2 to 8 carbon atoms. Among the 6 X groups in the molecule (i.e., 3 at each end of the molecular chain), at least two (especially, among the 3 X groups at each end of the molecular chain, at least one) are alkenyl groups. As the alkenyl group, a group having 2 to 8 carbon atoms, especially 2 to 6 carbon atoms and having a CH2=CH- structure at the end is preferred, and examples thereof include vinyl, allyl, propenyl, isopropenyl, butenyl, hexenyl, etc., among which vinyl and allyl are preferred. In the case where X is not an alkenyl group, in B 1 When it is a carbon atom, it becomes either a hydrogen atom or a methyl group. 1 When it is a silicon atom, a structure of a methyl group is formed.

[0094] In the above general formula (2), Rf 1 is a divalent perfluoropolyether group, containing -C a F 2a Examples of the repeating unit of O- (wherein a is an integer of 1 to 6) include a group represented by the following formula (11).

[0095] -(C g F 2g O) h -(11)

[0096] (In the formula, g is an integer of 1 to 6, and h is an integer of 5 to 600, preferably an integer of 10 to 400, and more preferably an integer of 30 to 200.)

[0097] As the above formula -C g F 2g Examples of the repeating unit represented by O- include units represented by the following formulae.

[0098] -CF2O-

[0099] -CF2CF2O-

[0100] -CF2CF2CF2O-

[0101] -CF(CF3)CF2O-

[0102] -CF2CF2CF2CF2O-

[0103] -CF2CF2CF2CF2CF2CF2O-

[0104] Among these, the unit represented by the following formula is particularly preferred.

[0105] -CF2O-

[0106] -CF2CF2O-

[0107] -CF2CF2CF2O-

[0108] -CF(CF3)CF2O-

[0109] The repeating unit in the divalent perfluoropolyether group may be composed of one of these alone or a combination of two or more thereof.

[0110] In addition, the divalent perfluoropolyether group preferably includes a structure of the following formula.

[0111] [Chemistry 17]

[0112]

[0113] (wherein G is a fluorine atom or a trifluoromethyl group, p1, q1 and r1 are each an integer satisfying p1≥0, q1≥0, 0≤p1+q1≤200, particularly 2≤p1+q1≤150 and 0≤r1≤6 (when p1+q1=0, 1≤r1≤6), k1, a1, s1, t1 and u1 are each an integer satisfying 1≤k1≤3, 2≤a1≤6, 0≤s1≤100, 0≤t1≤100, 2≤s1+t1≤200, 0≤u1≤6, particularly 2≤s1+t1≤150, 0≤u 1≤4, 2≤s1+t1+u1≤150, v1 and w1 are each an integer satisfying 1≤v1≤100, 1≤w1≤100, 2≤v1+w1≤200, z1 is an integer satisfying 1≤z1≤200, k1', a1' and a1" are each an integer satisfying 1≤k1'≤3, 1≤a1'≤6, 1≤a1"≤6, a1'≠a1", and z1' is an integer satisfying 1≤z1'≤200. The repeating units shown in () with v1 and w1 may be randomly bonded.)

[0114] In the above general formula (2), Rf 1 As specific examples, groups represented by the following formulae can be illustrated.

[0115] [Chemistry 18]

[0116]

[0117] (In the formula, p1, q1, r1, v1, w1, z1, and z1' are the same as those described above. s1' and t1' are each integers of 1 to 100, and s1'+t1'=2 to 200. t1" is an integer of 2 to 100. The repeating units shown in () with v1 and w1 may be randomly bonded.)

[0118] As the perfluoropolyether compound represented by the above general formula (2), in B 1 When it is a silicon atom, a compound represented by the following formula is particularly preferred: wherein Me is a methyl group and Et is an ethyl group.

[0119] [Chemistry 19]

[0120]

[0121] (s1' and t1' are each an integer of 1 to 100, and s1'+t1' is an integer of 2 to 200.)

[0122] [Chemistry 20]

[0123]

[0124] (s1' and t1' are each an integer of 1 to 100, and s1'+t1' is an integer of 2 to 200.)

[0125] [Chemistry 21]

[0126]

[0127] (s1' and t1' are each an integer of 1 to 100, and s1'+t1' is an integer of 2 to 200.)

[0128] [Chemistry 22]

[0129]

[0130] (s1' and t1' are each an integer of 1 to 100, and s1'+t1' is an integer of 2 to 200.)

[0131] [Chemistry 23]

[0132]

[0133] (s1' and t1' are each an integer of 1 to 100, and s1'+t1' is an integer of 2 to 200.)

[0134] As the perfluoropolyether compound represented by the above general formula (2), in B 1In the case of a carbon atom, a compound represented by the following formula is preferred.

[0135] [Chemistry 24]

[0136]

[0137] (v1 and w1 are each an integer of 1 to 100, and v1+w1 is an integer of 2 to 200. The repeating units shown in () with v1 and w1 may be randomly bonded.)

[0138] The amount of alkenyl groups contained in the perfluoropolyether compound of component (A) is preferably 0.002 to 0.3 mol / 100 g, and more preferably 0.008 to 0.12 mol / 100 g. When the amount of alkenyl groups contained in the perfluoropolyether compound is less than 0.002 mol / 100 g, the degree of crosslinking becomes insufficient, and curing disadvantages may occur, which is not preferred. When the amount of alkenyl groups exceeds 0.3 mol / 100 g, the mechanical properties of the cured product as a rubber elastic body may be impaired, which is not preferred. In the present invention, the amount of alkenyl groups can be 1 H-NMR measurement (same in Examples).

[0139] When the viscosity (23°C) of the perfluoropolyether compound of the component (A) is in the range of 40 to 100,000 mPa·s, more preferably 50 to 50,000 mPa·s, and even more preferably 60 to 20,000 mPa·s, it is preferred because the fluoropolyether curable composition of the present invention has suitable physical properties in the cured product when used for sealing, encapsulation, coating, impregnation, etc. Within this viscosity range, the most appropriate viscosity can be selected according to the application. In the present invention, the viscosity (23°C) can be measured using a rotational viscometer (e.g., BL type, BH type, BS type, cone and plate type, rheometer, etc.) (the same below).

[0140] (A) Component may be used alone or in combination of two or more of these perfluoropolyether compounds.

[0141] [(B) ingredient]

[0142] The component (B) used in the fluoropolyether curable composition of the present invention is characterized in that it is a fluorine-containing organohydrogensilane compound represented by the following general formula (1) and having two or more hydrosilyl groups, specifically, a compound having two or more hydrosilyl groups, wherein all the bonds between silicon atoms are composed of a silylene structure (the alkylene groups in the silylene structure may be fluorine-substituted alkylene groups partially substituted with fluorine), and the compound does not contain a siloxane bond.

[0143] [Chemistry 25]

[0144]

[0145] (In the formula, Rf is a monovalent perfluoropolyether group, A is a divalent organic group having 1 to 20 carbon atoms which may contain at least one selected from an oxygen atom, a nitrogen atom and a silicon atom, R is independently a monovalent hydrocarbon group having 1 to 6 carbon atoms, x is an integer of 1 to 3, B is independently a monovalent organic group having one or more diorganohydrogensilyl groups and forming a silylene structure with the connected silicon atom, and when x is 1, B has two or more diorganohydrogensilyl groups. y is 1 or 2.)

[0146] Rf in the above general formula (1) is a monovalent perfluoropolyether group. Rf is a group introduced to impart compatibility with the base oil in the fluoropolyether curable composition (particularly the thermosetting fluoropolyether composition). Compared with the perfluoroalkyl group, the perfluoropolyether group has a greater effect of imparting compatibility with the base oil by being introduced into the organohydrogensilane compound, and can form a fluoropolyether cured product with good properties.

[0147] In particular, Rf in the above general formula (1) is preferably a monovalent perfluoropolyether group represented by the following general formula (5).

[0148] [Chemistry 26]

[0149]

[0150] (In the formula, D is a fluorine atom or a perfluorooxyalkyl group having 1 to 6 carbon atoms, a, b, c and d are each independently an integer of 0 to 100, and are 2≤a+b+c+d≤100. Preferably, a is an integer of 0 to 50, b is an integer of 0 to 50, c is an integer of 0 to 50, d is an integer of 0 to 50, and are 5≤a+b+c+d≤50. More preferably, a is an integer of 0 to 10, b is an integer of 0 to 40, c is an integer of 0 to 30, d is an integer of 0 to 30, 6≤a+b+c+d≤40, and further preferably 7≤a+b+c+d≤30, and e is an integer of 1 to 3. The repeating units shown in () above may be randomly bonded, and these units may be linear or branched.)

[0151] In the above general formula (5), D is a fluorine atom or a perfluorooxyalkyl group having 1 to 6 carbon atoms. The perfluorooxyalkyl group having 1 to 6 carbon atoms is C g F 2g+1 It represents O-(g is an integer of 1 to 6), and specifically, groups represented by the following formulae are mentioned.

[0152] CF3O-

[0153] CF3CF2O-

[0154] CF3CF2CF2O-

[0155] CF3CF(CF3)O-

[0156] CF3CF2CF2CF2O-

[0157] CF3CF2CF2CF2CF2CF2O-

[0158] D is preferably a fluorine atom.

[0159] In the above general formula (5), when a+b+c+d is less than 2, the compatibility between the fluorinated organohydrogensilane compound and the base oil may be reduced, which is not preferred. On the other hand, when a+b+c+d is greater than 100, the viscosity of the fluorinated organohydrogensilane compound increases, and the viscosity of the fluoropolyether-based curable composition to which the fluorinated organohydrogensilane compound is added also increases excessively, which is not preferred.

[0160] Examples of the monovalent perfluoropolyether group represented by the general formula (5) include the following groups.

[0161] [Chemistry 27]

[0162]

[0163] (In the formula, g is an integer of 1 to 6, c' is an integer of 2 to 100, b' is an integer of 2 to 100, c", d' are each an integer of 0 to 100, c"+d' is an integer of 2 to 100, a' is an integer of 2 to 100, ca' is an integer of 1 to 99. The repeating units shown in () with c" and d' may be randomly bonded.)

[0164] In the above general formula (1), A is a divalent organic group having 1 to 20 carbon atoms which may contain at least one selected from an oxygen atom, a nitrogen atom and a silicon atom, and is preferably a divalent hydrocarbon group having 1 to 20 carbon atoms which may contain at least one selected from an oxygen atom, a nitrogen atom and a silicon atom, and examples thereof include an alkylene group having 1 to 12 carbon atoms, an alkylene group having 1 to 12 carbon atoms containing an arylene group having 6 to 8 carbon atoms (for example, an alkylene-arylene group having 8 to 20 carbon atoms), and alkylene groups having 1 to 10 carbon atoms which are mutually connected. A divalent group bonded by a diorganosilylene group, a divalent group bonded by an alkylene group having 1 to 10 carbon atoms and an arylene group having 6 to 8 carbon atoms via a diorganosilylene group, and a divalent group further having at least one selected from an ether bond oxygen atom, a secondary amino group (imino group), a tertiary amino group (substituted imino group) and an amide bond in these groups, etc., wherein it is preferred that a divalent group containing at least one selected from an ether bond oxygen atom, a secondary amino group (imino group), a tertiary amino group (substituted imino group) and an amide bond is contained in the molecular chain. Furthermore, when A contains a silicon atom (diorganosilylene group), it is preferred that a silanylene structure is formed in which the silicon atom (diorganosilylene group) is bonded to the silicon atom bonded to A via an alkylene group (preferably an unsubstituted or fluorine-substituted alkylene group having 1 to 12 carbon atoms, more preferably an ethylene group).

[0165] Specifically, A is preferably a group represented by any one of the following general formulae (6) to (9).

[0166] [Chemistry 28]

[0167]

[0168] (Where X 0 is a hydrogen atom, a methyl group or an ethyl group, X 1 are independently a hydrogen atom, a fluorine atom, a methyl group, an ethyl group or a trifluoromethyl group, X 2 is a hydrogen atom, a methyl group, an ethyl group, an isopropyl group or a phenyl group, R' is independently a methyl group or an ethyl group, f is an integer of 1 to 6, and t is 0 or 1. In addition, the bonding end with * indicates bonding to the Si atom in the above general formula (1), and the bonding end without a mark indicates bonding to Rf.)

[0169] Examples of the structure of A represented by the general formulae (6) to (9) include the following.

[0170] [Chemistry 29]

[0171]

[0172] [Chemistry 30]

[0173]

[0174] [Chemistry 31]

[0175]

[0176] (In the formula, Me is a methyl group, and Et is an ethyl group. The bonding end with * indicates bonding to the Si atom in the above general formula (1), and the bonding end without a mark indicates bonding to Rf.)

[0177] R in the general formula (1) is independently a monovalent hydrocarbon group having 1 to 6 carbon atoms, and specifically, preferably a methyl group, an ethyl group, an isopropyl group, a tert-butyl group, or a phenyl group, and more preferably a methyl group or an ethyl group.

[0178] B in the above general formula (1) is a monovalent organic group having one or more diorganohydrogensilyl groups and forming a silylene structure with the silicon atom to which it is connected, that is, when x is 1, it has two or more, preferably 2 to 5 diorganohydrogensilyl groups, and when x is 2 or 3, it is independently a monovalent silicon-containing organic group having one or more, preferably 1 to 3 diorganohydrogensilyl groups and forming a silylene structure with the silicon atom to which it is connected, and does not contain a siloxane bond. In addition, the silylene structure is preferably an alkylene group R having 1 to 12 carbon atoms in which the silicon atoms are connected via unsubstituted and / or fluorine-substituted alkylene groups R A In addition, B preferably has one or more silicon atoms, more preferably 1 to 6, and even more preferably 1 to 4. In formula (1), such B is bonded to the silicon atom with 1 to 3 (x=an integer of 1 to 3), preferably 2 or 3 (preferably, x is 2 or 3).

[0179] In addition, preferably, the silylene structure connected in the molecular chain between Rf in the general formula (1) and the diorganohydrogensilyl group in B (i.e., the structure containing -A-Si-, -Si-(CH2) in the formula) y -Si- and -Si-B, continuous silylene bonds (-Si-R A The number of -Si-)) is 2 or more, and more preferably 2, 3 or 4.

[0180] B is preferably represented by the following general formula (10).

[0181] [Chemistry 33]

[0182]

[0183] [wherein, p is an integer of 1 to 6, preferably an integer of 1 to 4, q is an integer of 0 to 6, preferably an integer of 0 or 4 to 6, r is an integer of 1 to 3, R is the same as above, and E is a hydrogen atom or a

[0184] [Chemistry 34]

[0185]

[0186] A group represented by (wherein R is the same as above, p' is an integer of 1 to 6, preferably an integer of 1 to 4, and q' is an integer of 0 to 6, preferably an integer of 0 or 4 to 6.) (However, when E is a hydrogen atom, r is 1.) The repeating units shown in () with the above p, q or p', q' may be randomly bonded.]

[0187] R in the above general formula (10) is the same as R in the above general formula (1), and is a monovalent hydrocarbon group having 1 to 6 carbon atoms, among which methyl, ethyl, propyl, isopropyl, tert-butyl and phenyl are particularly preferred.

[0188] Examples of B in the general formula (1) include the following groups.

[0189] [Chemistry 35]

[0190]

[0191] [Chemistry 36]

[0192]

[0193] [Chemistry 37]

[0194]

[0195] (In the formula, Me is methyl, Et is ethyl, iPr is isopropyl, tBu is tert-butyl, and Ph is phenyl.)

[0196] Examples of the fluorine-containing organohydrogensilane compound represented by the general formula (1) include the following compounds.

[0197] [Chemistry 38]

[0198]

[0199] [Chemistry 39]

[0200]

[0201] [Chemistry 40]

[0202]

[0203] [Chemistry 41]

[0204]

[0205] [Chemistry 42]

[0206]

[0207] [Chemistry 43]

[0208]

[0209] [Chemistry 44]

[0210]

[0211] (In the formula, b' is an integer of 2 to 100, c'' and d'' are each an integer of 1 to 99, c'' + d'' = an integer of 2 to 100, ca' is an integer of 1 to 99, Me is a methyl group, Et is an ethyl group, and Ph is a phenyl group. The repeating units shown in () with c'' and d'' may be randomly bonded.)

[0212] [Method for producing fluorine-containing organohydrogensilane compound]

[0213] The method for producing the fluorinated organohydrogensilane compound represented by the general formula (1) as component (B) preferably comprises a step of introducing two or more diorganohydrogensilyl groups into the fluorinated compound with a prescribed connecting structure by, for example, a hydrosilylation reaction of a fluorinated compound containing an alkenyl group (vinyl group, allyl group, etc.) represented by the general formula (1A) below with an organohydrogensilane compound having at least three diorganohydrogensilyl groups represented by the general formula (1B) below.

[0214] [Chemistry 45]

[0215]

[0216] [Chemistry 46]

[0217]

[0218] In the general formula (1A), A 2 It is a divalent organic group having 1 to 18 carbon atoms which may contain at least one selected from an oxygen atom, a nitrogen atom and a silicon atom. The description of Rf, R, B, y and x in the above general formulae (1A) and (1B) is the same as the description of Rf, R, B, y and x in the above general formulae (1). That is, in the above general formulae (1A) and (1B), Rf is a monovalent perfluoropolyether group, R is independently a monovalent hydrocarbon group having 1 to 6 carbon atoms, x is an integer of 1 to 3, B is independently a monovalent organic group having one or more diorganohydrogensilyl groups and forming a silylene structure with the connected silicon atom, and when x is 1, B has two or more diorganohydrogensilyl groups. y is 1 or 2.

[0219] A 2is a divalent organic group (preferably a hydrocarbon group) having 1 to 18 carbon atoms which may contain at least one selected from an oxygen atom, a nitrogen atom and a silicon atom, and examples thereof include an alkylene group having 1 to 10 carbon atoms, an alkylene group having 1 to 10 carbon atoms containing an arylene group having 6 to 8 carbon atoms (for example, an alkylene-arylene group having 7 to 18 carbon atoms), a divalent group in which a diorganosilylene group is bonded to an alkylene group having 1 to 10 carbon atoms, a divalent group in which a diorganosilylene group is bonded to an arylene group having 6 to 8 carbon atoms, an alkylene group having 1 to 10 carbon atoms and A divalent group in which an alkylene group having 1 to 8 carbon atoms is bonded via a diorganosilylene group, a divalent group in which an alkylene group having 1 to 8 carbon atoms and an arylene group having 6 to 8 carbon atoms are bonded via a diorganosilylene group, and a divalent group in which these groups further have at least one selected from an ether bond oxygen atom, a secondary amino group (imino group), a tertiary amino group (substituted imino group) and an amide bond, etc. Among them, a divalent group containing at least any one selected from an ether bond oxygen atom, a secondary amino group (imino group), a tertiary amino group (substituted imino group) and an amide bond in the molecular chain is preferred.

[0220] As A 2 , specifically, it is preferably represented by any one of the following general formulae.

[0221] [Chemistry 47]

[0222]

[0223] [Chemistry 48]

[0224]

[0225] (Where X 0 , X 1 , X 2 and f are the same as above, and their explanations are the same as those of X in the above formula (1). 0 , X 1 , X 2 , f' is the same as the description. f' is an integer of 0 to 4. The bonding end with * indicates bonding to the vinyl group of the above general formula (1A), and the bonding end without a mark indicates bonding to Rf.

[0226] As A represented by the above general formula 2 The structural examples include, for example, the following structural examples.

[0227] [Chemistry 49]

[0228]

[0229] [Chemistry 50]

[0230]

[0231] [Chemistry 51]

[0232]

[0233] [Chemistry 52]

[0234]

[0235] (In the formula, Me is a methyl group, and Et is an ethyl group. The bonding end with * indicates bonding to the vinyl group of the above general formula (1A), and the bonding end without a symbol indicates bonding to Rf.)

[0236] The production process (reaction formula) of a preferred method for producing a fluorinated organohydrogensilane compound is shown below.

[0237] [Chemistry 53]

[0238]

[0239] The explanations of Rf, A, R, B, y, and x in the reaction formula shown in the above step are the same as the explanations of Rf, A, R, B, y, and x in the above general formula (1). 2 The description is the same as that of A in the above general formula (1A) 2 M is a metal catalyst.

[0240] In the above process, a fluorine-containing organic hydrogen silane compound represented by the above general formula (1) is produced by subjecting a fluorine-containing compound represented by the above general formula (1A) having an alkenyl group (preferably a vinyl group or an allyl group) at the end of the molecular chain to a hydrosilylation reaction with an organic hydrogen silane compound represented by the above general formula (1B) having at least 3 diorganohydrogen silyl groups in the molecule in the presence of a metal catalyst (M).

[0241] In the above reaction, as the fluorine-containing compound represented by the above general formula (1A) and having an alkenyl group (preferably a vinyl group or an allyl group) at the end of the molecular chain, for example, the following compounds can be used.

[0242] [Chemistry 54]

[0243]

[0244] (In the formula, b' is an integer of 2 to 100, c'' and d'' are each an integer of 1 to 99, c'' + d'' = an integer of 2 to 100, ca' is an integer of 1 to 99, Me is a methyl group, and Et is an ethyl group. The repeating units shown in () with c'' and d'' may be randomly bonded.)

[0245] As the organohydrogensilane compound represented by the general formula (1B) and having at least three diorganohydrogensilyl groups in the molecule, for example, the following compounds can be used.

[0246] [Chemistry 55]

[0247]

[0248] [Chemistry 56]

[0249]

[0250] (In the formula, Me is methyl, Et is ethyl, and Ph is phenyl.)

[0251] The amount of the fluorinated compound represented by the general formula (1A) having an alkenyl group (preferably a vinyl group or an allyl group) at the end of the molecular chain is such that the amount of the alkenyl group of the fluorinated compound is 0.16 to 0.30 equivalents, preferably 0.20 to 0.25 equivalents, relative to the amount of the hydrosilyl group of the compound represented by the general formula (1B). If the amount of the alkenyl group of the fluorinated compound is less than 0.16 equivalents relative to the amount of the hydrosilyl group of the compound represented by the general formula (1B), the following disadvantages may occur: when the obtained fluorinated organohydrogensilane compound is added to a fluoropolyether-based curable composition, white turbidity and increased viscosity may occur, and uncured portions may be scattered on the surface of the cured product obtained by thermal curing, which is not preferred. If the amount of alkenyl groups in the fluorinated compound is more than 0.30 equivalents relative to the amount of hydrosilyl groups in the compound represented by the general formula (1A), the amount of hydrosilyl groups in the resulting fluorinated organohydrogensilane compound becomes excessively small, and the fluoropolyether curable composition becomes difficult to cure, which is not preferred.

[0252] In addition, the above reaction step can rapidly carry out hydrosilylation by adding M (metal catalyst). M is not particularly limited as long as it is a metal catalyst that can be a catalyst for hydrosilylation, and compounds containing metal atoms such as platinum, rhodium, ruthenium, palladium, etc. can be preferably used. For example, chloroplatinic acid or a complex of chloroplatinic acid with an olefin such as ethylene, a complex with an alcohol or vinylsiloxane, metal platinum supported on silica, alumina, carbon, etc., RhCl(PPh3)3, RhCl(CO)(PPh3)2, Ru3(CO) 12 , IrCl(CO)(PPh3)2, Pd(PPh3)4, etc. In the above formula, Ph is phenyl. Among them, platinum compounds are particularly preferred.

[0253] When these are used as catalysts, they can also be used in a solid state when they are solid catalysts. In order to make the reaction proceed more rapidly, it is preferred to use a solution obtained by dissolving the above metal catalyst in an appropriate solvent. When adding, it is preferably confirmed that the fluorine-containing compound represented by the above general formula (1A) having an alkenyl group (preferably a vinyl group or an allyl group) at the end of the molecular chain and the organohydrogensilane compound represented by the above general formula (1B) having at least 3 diorganohydrogensilyl groups in the molecule are heated to a prescribed temperature and then dripped. The so-called prescribed temperature is preferably above 50°C, more preferably above 65°C.

[0254] When the fluorine-containing compound represented by the above general formula (1A) having an alkenyl group (preferably a vinyl group or an allyl group) at the end of the molecular chain and the organohydrogensilane compound represented by the above general formula (1B) having at least three diorganohydrogensilyl groups in the molecule are solid or the compounds are insoluble in each other, they can be dissolved in a small amount of organic solvent and then M (metal catalyst) can be added. Examples of usable solvents include benzene, toluene, xylene, 1,3-bis(trifluoromethyl)benzene, and the like, preferably 1,3-bis(trifluoromethyl)benzene.

[0255] The amount of hydrosilyl groups in the fluorinated organohydrogensilane compound of component (B) is preferably 0.05 to 0.35 mol / 100 g, more preferably 0.06 to 0.30 mol / 100 g. 1 H-NMR measurement (same in Examples).

[0256] The amount of the component (B) is such that the hydrogen atoms (hydrosilyl groups, i.e., Si-H groups) bonded to silicon atoms in the component (B) are 0.1 to 2.5 moles, preferably 0.2 to 2 moles, per 1 mole of alkenyl groups such as vinyl groups and allyl groups in the component (A). If the amount of the hydrosilyl groups is too small, the degree of crosslinking becomes insufficient, resulting in no cured product. If the amount of the hydrosilyl groups is too large, foaming occurs during curing.

[0257] In the method for producing the fluorinated organic hydrogen silane compound of component (B), the target product is separated after the reaction is completed. In addition, as long as the characteristics of the present invention are not impaired, the mixture containing unreacted products or by-products can also be used by removing the addition reaction catalyst. In all cases, as long as 0.1 to 2.5 moles, preferably 0.2 to 2 moles of hydrosilyl groups, i.e., Si-H groups, are included relative to 1 mole of alkenyl groups such as vinyl and allyl groups in component (A).

[0258] As the component (B), these fluorinated organohydrogensilane compounds may be used alone or in combination of two or more.

[0259] [(C) ingredient]

[0260] The component (C) used in the fluoropolyether curable composition of the present invention is a platinum group metal catalyst. It is a hydrosilylation reaction catalyst, and is a catalyst that promotes the addition reaction of the alkenyl group in the component (A), the component (B), and the hydrosilyl group in the adhesion enhancer or adhesion promoter described later as an optional component. The hydrosilylation reaction catalyst is generally a compound of a noble metal, and due to its high price, platinum or a platinum compound that is relatively easy to obtain is often used.

[0261] Examples of platinum compounds include chloroplatinic acid or a complex of chloroplatinic acid with an olefin such as ethylene, a complex with an alcohol or vinylsiloxane, and metal platinum supported on silica, alumina, carbon, etc. Rhodium, ruthenium, iridium, and palladium compounds are also known as platinum group metal catalysts other than platinum compounds, and examples thereof include RhCl(PPh3)3, RhCl(CO)(PPh3)2, Ru3(CO) 12 , IrCl(CO)(PPh3)2, Pd(PPh3)4, etc. In the above formula, Ph is a phenyl group.

[0262] When these are used as catalysts, they can be used in a solid state if they are solid catalysts. To obtain a more uniform cured product, it is preferred to use a solution prepared by dissolving chloroplatinic acid or its complex in an appropriate solvent and the perfluoropolyether compound of the component (A).

[0263] The amount of component (C) used may be a catalytic amount, for example, preferably 0.1 to 1000 ppm (calculated as platinum group metal atoms), more preferably 1 to 500 ppm, relative to the mass of component (A). Component (C) may be used alone or in combination of two or more.

[0264] [(D) ingredient]

[0265] The component (D) used in the fluoropolyether curable composition of the present invention is a filler selected from at least one of organic resin powder and carbon black powder, and is used to improve the mechanical properties such as hardness, tensile strength, and elongation at break of the cured product obtained from the fluoropolyether curable composition.

[0266] In the component (D), there is no limitation on the type of organic resin powder as long as it is durable to strong acid. Specifically, polyimide resin (PI) powder, polytetrafluoroethylene resin (PTFE) powder, polyphenylene sulfide resin (PPS) powder, polyetheretherketone resin (PEEK) powder, polyphenylsulfone resin powder, polyetherimide resin (PEI) powder, polypropylene resin (PP) powder, etc. can be cited. From the viewpoint of durability and reinforcement to strong acid, polyimide resin powder is preferred.

[0267] In the component (D), examples of the carbon black powder include furnace black powder, lamp black powder, acetylene black powder, channel black powder, and the like, and acetylene black powder is preferred.

[0268] The smaller the average particle size of the component (D), the more preferably it can be used in the fluoropolyether curable composition of the present invention. Specifically, it is 0.001 to 100 μm, preferably 0.001 to 30 μm, and more preferably 0.001 to 15 μm. When the average particle size of the component (D) is larger than 100 μm, the effect of improving the mechanical properties of the cured product obtained from the fluoropolyether curable composition may be reduced. In addition, if the average particle size of the component (D) is smaller than 0.001 μm, the component (D) may be separated from other liquid components (particularly the component (A)) over time during long-term storage in the fluoropolyether curable composition. In addition, the average particle size can be obtained as the cumulative volume average diameter (D50 or median diameter) in the particle size distribution measurement using the laser diffraction scattering method (the same below).

[0269] As the component (D), a pulverized organic resin powder, preferably a polyimide resin powder is more preferred. By reducing the average particle size of the organic resin powder by pulverization, the amount that can be filled into the fluoropolyether-based curable composition can be increased.

[0270] The average particle size of the organic resin powder subjected to the pulverization treatment is preferably 0.001 to 5 μm, more preferably 0.001 to 3 μm, and still more preferably 0.001 to 2.8 μm. If the average particle size is 5 μm or less, the amount that can be filled in the fluoropolyether curable composition is increased, and the effect of improving the mechanical properties of the obtained cured product is further increased.

[0271] The type of pulverizer for pulverizing the organic resin powder is not particularly limited as long as the average particle size is finished to be 5 μm or less. Specifically, a roller mill, jet mill, hammer mill, pin mill, rotary mill, vibration mill, planetary mill, attritor, bead mill or the like can be used. The pulverization conditions are not particularly limited as long as the average particle size of the organic resin powder is 5 μm or less.

[0272] The component (D) may be used alone or in combination of two or more. In particular, polyimide resin powder and / or carbon black powder, and pulverized polyimide resin powder are preferred.

[0273] The amount of component (D) is 0.1 to 200 parts by mass, preferably 1 to 100 parts by mass, relative to 100 parts by mass of component (A). If the amount of component (D) is less than 0.1 parts by mass relative to 100 parts by mass of component (A), the effect of improving the mechanical properties of the cured product obtained from the fluoropolyether curable composition is reduced, so it is not preferred. If the amount of component (D) exceeds 200 parts by mass relative to 100 parts by mass of component (A), the viscosity of the fluoropolyether curable composition increases significantly, and the workability (handling property) is poor, so it is not preferred. When a pulverized organic resin powder is used as the component (D), it is preferred to mix 10 to 200 parts by mass, particularly 30 to 100 parts by mass, relative to 100 parts by mass of the component (A) in order to suppress the separation of the component (D) from other liquid components (particularly the component (A)) in the fluoropolyether curable composition over time and to avoid deterioration in workability (handling properties) due to a significant increase in the viscosity of the fluoropolyether curable composition.

[0274] [Other ingredients]

[0275] In order to improve the practicality of the fluoropolyether curable composition of the present invention, in addition to the above-mentioned components (A) to (D), various compounding agents such as an adhesion enhancer (adhesion imparting agent), a plasticizer, a viscosity modifier, a flexibility imparting agent, a hydrosilylation reaction catalyst control agent, an inorganic filler (however, excluding the carbon black powder of the component (D)), an adhesion promoter, and a silane coupling agent may be added as needed. The amount of these additives added is optional as long as it does not impair the purpose of the present invention and does not impair the characteristics of the composition and the physical properties of the cured product.

[0276] The adhesion improver functions as an adhesion improver for making the fluoropolyether curable composition of the present invention exhibit self-adhesion by compounding, and is an organohydrogenpolysiloxane compound having one or more hydrogen atoms (Si-H groups) bonded to silicon atoms, epoxy groups bonded to silicon atoms via carbon atoms or carbon atoms and oxygen atoms, and / or trialkoxysilyl groups in each molecule. Furthermore, the adhesion improver has a molecular structure equivalent to that of fluorine-containing organohydrogensiloxane, so the use of the adhesion improver is extremely effective in the case of requiring initial self-adhesion in the manufacturing process of an article having a cured product obtained from the fluoropolyether curable composition of the present invention, although it is difficult to maintain long-term self-adhesion to hydrofluoric acid and an electrolyte for lithium ion secondary batteries.

[0277] In the above-mentioned adhesion improver, it is more preferred to further have one or more perfluoroalkyl groups or monovalent perfluoropolyether groups (perfluorooxyalkyl groups) in one molecule which are bonded to the silicon atom via a divalent linking group containing at least one selected from oxygen atoms, nitrogen atoms, carbon atoms and silicon atoms, particularly bonded to the silicon atom via a divalent linking group containing nitrogen atoms and carbon atoms or bonded to the silicon atom via a divalent linking group containing nitrogen atoms, carbon atoms and oxygen atoms. Examples of such perfluoroalkyl groups include C j F 2j+1 -(j is an integer of 1 to 10, preferably an integer of 3 to 7.) As the monovalent perfluoropolyether group, the same groups as those exemplified in Rf of formula (1) shown in the above-mentioned (B) component can be exemplified. As the divalent linking group connecting the perfluoroalkyl group or the monovalent perfluoropolyether group to the silicon atom, a divalent organic group (preferably a hydrocarbon group) having 1 to 20 carbon atoms and containing at least one selected from an oxygen atom, a nitrogen atom and a silicon atom can be used.

[0278] The siloxane skeleton of the organohydrogenpolysiloxane compound as the adhesion improver may be any of cyclic, linear, branched, etc., or a mixture of two or more thereof, but is preferably cyclic. As the organohydrogenpolysiloxane compound as the adhesion improver, a compound represented by the following general formula can be used.

[0279] [Chemistry 57]

[0280]

[0281] (Where R 2 is an unsubstituted or halogen-substituted monovalent hydrocarbon group, L 1 is a monovalent perfluoropolyether group bonded to the silicon atom via a divalent linking group, M 1 It is an epoxy group or a trialkoxysilyl group bonded to a silicon atom via a carbon atom or a carbon atom and an oxygen atom as shown below. w2 is preferably an integer satisfying 0≤w2≤50, more preferably an integer satisfying 0≤w2≤20, x2 is preferably an integer satisfying 1≤x2≤50, more preferably an integer satisfying 1≤x2≤20, y2 is preferably an integer satisfying 0≤y2≤50, more preferably an integer satisfying 1≤y2≤20, z2 is preferably an integer satisfying 1≤z2≤50, more preferably an integer satisfying 1≤z2≤20. Each repeating unit shown in the above () may be randomly bonded. )

[0282] As the above R 2The unsubstituted or halogen-substituted monovalent hydrocarbon group is preferably a monovalent hydrocarbon group containing no aliphatic unsaturated bond and having 1 to 10 carbon atoms, and more preferably a monovalent hydrocarbon group having 1 to 8 carbon atoms. Specifically, examples include alkyl groups such as methyl, ethyl, propyl, butyl, hexyl, cyclohexyl, and octyl; aryl groups such as phenyl and tolyl; aralkyl groups such as benzyl and phenylethyl; substituted monovalent hydrocarbon groups in which a part or all of the hydrogen atoms of these groups are substituted with halogen atoms such as fluorine, etc., among which methyl is particularly preferred.

[0283] The above L 1 It is a monovalent perfluoropolyether group bonded to a silicon atom via a divalent linking group and is preferably represented by the following general formula.

[0284] -Z-Rf 2

[0285] [Wherein, Rf 2 is a monovalent perfluoropolyether group, which is the same as Rf in the above general formula (1), and can be exemplified by the same groups as those exemplified in Rf. Z is a divalent organic group (preferably a hydrocarbon group) having 1 to 20 carbon atoms and which may contain at least one selected from oxygen atoms, nitrogen atoms and silicon atoms.]

[0286] Examples of Z include -CH2-*, -CH2CH2CH2-*, -OCH2-*, -CH2OCH2-*, -(CH2)2OCH2-*, -(CH2)3OCH2-*, -CH2-NH-CO-*, -(CH2)3-NH-CO-*, -(CH2)3-N(CH3)-CO-*, -(CH2)3-N(CH2CH3)-CO-*, -(CH2)3-N(CH(CH3)2)-CO-*, -CH2-N(Ph)-CO-*, -(CH2)3-O-CO-*, -CH2OCH2CH2CH2-Si(CH3)2-O-Si(CH3)2)-CO-*, and -CH2-N(Ph)-CO-*. H3)2-(CH2)2-*, -CO-N(CH3)-Ph'-Si(CH3)2-(CH2)2-*, -CO-N(CH2)-Ph'-Si(CH2)2-(CH2)2-Si(CH2)2-O-Si(CH2)2-(CH2)2-*, -CO-NH-Ph'-[Si(CH3)2-(CH2)2]3-CH2-*, -CO-N(CH3)-Ph'-[Si(CH3)2-(CH2)2]3-*, and groups represented by the following general formula, among which -(CH2)3OCH2-*, -(CH2)3-NH-CO-*, and groups represented by the following general formula are preferred. In addition, Ph represents a phenyl group, and Ph' represents a phenylene group. In addition, the bonding end with * indicates bonding to a monovalent perfluoropolyether group, and the bonding end without * indicates bonding to a silicon atom in the organohydrogenpolysiloxane.

[0287] [Chemistry 58]

[0288]

[0289] The above M 1 It represents an epoxy group or a trialkoxysilyl group bonded to a silicon atom via a carbon atom or a carbon atom and an oxygen atom, and specifically includes the following groups.

[0290] [Chemistry 59]

[0291]

[0292] (Where R 3 It represents a divalent hydrocarbon group having 1 to 10 carbon atoms, especially 1 to 5 carbon atoms, which may have an oxygen atom (alkylene groups such as methylene, ethylene, and propylene, cycloalkylene groups such as cyclohexylene, oxyalkylene groups such as oxyethylene, oxypropylene, and oxybutylene, etc., preferably -(CH2)3OCH2-*' (a bonding end with *' indicates bonding to an epoxy group)).

[0293] -R 4 -Si(OR 5 )3

[0294] (Where R 4 represents a divalent hydrocarbon group having 1 to 10 carbon atoms, particularly 1 to 4 carbon atoms (such as an alkylene group such as a methylene group, an ethylene group, or a propylene group), R 5 Each of the groups independently represents a monovalent hydrocarbon group having 1 to 8 carbon atoms, particularly 1 to 4 carbon atoms (such as an alkyl group such as a methyl group, an ethyl group, a propyl group, or a butyl group).

[0295] [Chemistry 60]

[0296]

[0297] (Where R 6 is a hydrogen atom or a methyl group, R 7 Each of the groups independently represents a monovalent hydrocarbon group having 1 to 8 carbon atoms, particularly a monovalent hydrocarbon group having 1 to 4 carbon atoms (such as an alkyl group such as a methyl group, an ethyl group, a propyl group, or a butyl group), and l represents an integer of 2 to 10.

[0298] The organohydrogenpolysiloxane compound used as the adhesion improver can be obtained by subjecting an organohydrogenpolysiloxane having three or more hydrogen atoms bonded to silicon atoms (Si-H groups) in one molecule to a partial addition reaction with a compound containing an aliphatic unsaturated group such as a vinyl group or an allyl group and an epoxy group and / or a trialkoxysilyl group, and further, if necessary, a compound containing an aliphatic unsaturated group and a perfluoroalkyl group or a perfluorooxyalkyl group, according to a conventional method. In addition, the number of the above-mentioned aliphatic unsaturated groups must be less than the number of Si-H groups.

[0299] In the production of an organohydrogenpolysiloxane compound used as an adhesion improver, the target product may be isolated after the reaction is completed, or a mixture obtained by removing only unreacted products and an addition reaction catalyst may be used.

[0300] As the organohydrogen polysiloxane compound used as the adhesion improver, specifically, compounds represented by the following structural formulas can be exemplified. These compounds can be used alone or in combination of two or more. In the following formula, Me represents a methyl group.

[0301] [Chemistry 61]

[0302]

[0303] (In the formula, x2'=2 or 3, b1'=an integer from 2 to 20. The repeating units shown in () may be randomly bonded.)

[0304] [Chemistry 62]

[0305]

[0306] (In the formula, x2'=2 or 3, b1'=an integer from 2 to 20. The repeating units shown in () may be randomly bonded.)

[0307] [Chemistry 63]

[0308]

[0309] (In the formula, x2'=1 or 2, b1'=an integer from 2 to 20. The repeating units shown in () may be randomly bonded.)

[0310] [Chemistry 64]

[0311]

[0312] (In the formula, z2'=2 or 3, b1'=an integer from 2 to 20. The repeating units shown in () may be randomly bonded.)

[0313] [Chemistry 65]

[0314]

[0315] (In the formula, y2'=2 or 3, b1'=an integer from 2 to 20. The repeating units shown in () may be randomly bonded.)

[0316] The amount of the adhesion improver when added is preferably such that the hydrosilyl groups (Si—H groups) in the adhesion improver are 0.005 to 0.5 mol, more preferably 0.01 to 0.2 mol, and even more preferably 0.05 to 0.1 mol per 1 mol of alkenyl groups in the component (A).

[0317] As the plasticizer, viscosity modifier and flexibility imparting agent, a polyfluoromonoalkenyl compound represented by the following general formula (12) and / or a polyfluoro compound represented by the following general formula (13) or (14) may be used in combination.

[0318] R 3 -(Z 1 ) p2 CH=CH2 (12)

[0319] [Where Z 1 is a divalent organic group (preferably a hydrocarbon group) having 1 to 20 carbon atoms and which may contain at least one selected from an oxygen atom, a nitrogen atom and a silicon atom, p2 is 0 or 1, Rf 3 It is a monovalent perfluoropolyether group represented by the following general formula.

[0320] [Chemistry 66]

[0321]

[0322] (wherein, f2 is an integer of 2 to 200, preferably an integer of 2 to 100, and h2 is an integer of 1 to 3, and is greater than Rf in the formula (2) in the component (A) used. 1 The molecular weight is small. )]

[0323] Y 1 -O-(CF2CF2CF2O) c2 -Y 1 (13)

[0324] [Wherein, Y 1 Independently by formula: C k2 F 2k2+1 -(k2 is an integer of 1 to 3), c2 is an integer of 1 to 200, and is smaller than Rf in the formula (2) in the component (A) used. 1 The molecular weight is small.]

[0325] Y 2 -O-(CF2O) d2 (CF2CF2O) e2 -Y 2 (14)

[0326] (Where Y 2 With the above Y 1The same, d2 and e2 are each an integer of 1 to 200, and are greater than Rf in the formula (2) in the component (A) used. 1 The molecular weight is small. The repeating units shown in the above () can be randomly bonded. )

[0327] In the above general formula (12), Z 1 is a divalent organic group (preferably a hydrocarbon group) having 1 to 20 carbon atoms and which may contain at least one selected from an oxygen atom, a nitrogen atom and a silicon atom, except for the above L 1 In addition to the same Z (divalent linking group) in the structure, the following groups can be exemplified (in the following and the exemplified formulas of Z, the bonding end with * represents the bonding end with Rf 3 Bonding, the bonding end without * indicates bonding to a carbon atom. )

[0328] [Chemistry 67]

[0329]

[0330] Specific examples of the polyfluoromonoalkenyl compound represented by the general formula (12) include the following examples: Furthermore, the following f2 satisfies the above-mentioned necessary characteristics.

[0331] [Chemistry 68]

[0332]

[0333] Specific examples of the polyfluorinated compounds represented by the general formulae (13) and (14) include the following examples: Furthermore, c2, d2, e2, and the sum of d2 and e2 satisfy the above-mentioned necessary characteristics.

[0334] CF3O-(CF2CF2CF2O) c2 -CF2CF3

[0335] CF3-O-(OCF2) d2 (OCF2CF2) e2 -CF3

[0336] The viscosity (23° C.) of the polyfluorinated compounds of the formulae (12), (13) and (14) is preferably in the range of 2000 to 50000 mPa·s.

[0337] The amount of the polyfluorinated compounds of the formulae (12), (13) and (14) to be added is preferably 1 to 300 parts by mass, more preferably 50 to 250 parts by mass, based on 100 parts by mass of the component (A).

[0338] In addition, as a control agent for the hydrosilylation reaction catalyst, for example, acetylene cyclohexanol (another name: 1-ethynyl-1-hydroxycyclohexane), 3-methyl-1-butyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol, 3-methyl-1-pentene-3-ol, phenylbutynol and other acetylene alcohols, reaction products of chlorosilanes having the above-mentioned monovalent fluorine-containing substituents and acetylene alcohols, 3-methyl-3-pentene-1-yne, 3,5-dimethyl-3-hexene-1-yne, triallyl isocyanurate, or polyvinylsiloxane, organic phosphorus compounds, etc. can be listed, and by adding them, curing reactivity and storage stability can be appropriately maintained. The amount of the control agent when mixing is arbitrary within the range that can provide the target curability and storage stability.

[0339] As the inorganic filler (but excluding the carbon black powder of the component (D)), for example, silica powders such as fumed silica (fumed silica or dry-process silica), precipitated silica (wet-process silica), spherical silica (fused silica), sol-gel silica, and silica aerosol, various surface-treated silica powders obtained by hydrophobizing the untreated surface of the silica powder with various organochlorosilanes, organodisilazanes, cyclic organopolysilazanes, etc., quartz powder, fused quartz powder, diatomaceous earth, and reinforcing or quasi-reinforcing fillers such as calcium carbonate, inorganic pigments such as titanium oxide, iron oxide, and cobalt aluminate, heat resistance improvers such as titanium oxide, iron oxide, cerium oxide, cerium hydroxide, zinc carbonate, magnesium carbonate, and manganese carbonate, thermal conductivity imparting agents such as aluminum oxide, boron nitride, silicon carbide, and metal powder, and conductivity imparting agents such as silver powder and conductive zinc oxide, etc. can be added.

[0340] The amount of the inorganic filler when added is preferably 0.1 to 100 parts by mass, more preferably 1 to 60 parts by mass, based on 100 parts by mass of the component (A).

[0341] When the adhesion improver is included, the adhesion promoter is a substance for improving the adhesion imparting ability of the adhesion improver and promoting the self-adhesion of the cured product obtained by curing the fluoropolyether curable composition of the present invention. In particular, carboxylic anhydride can be preferably used.

[0342] Examples of the carboxylic anhydride include carboxylic anhydrides that are solid at 23° C. Specifically, the following compounds can be exemplified. In the following formula, Me represents a methyl group.

[0343] [Chemistry 69]

[0344]

[0345] In addition, as the carboxylic anhydride, a cyclic organopolysiloxane having a hydrogen atom directly bonded to a silicon atom, a perfluoroalkyl group or a perfluorooxyalkyl group bonded to a silicon atom via a divalent hydrocarbon group that may contain at least one selected from an oxygen atom, a nitrogen atom and a silicon atom, and a cyclic carboxylic anhydride residue bonded to a silicon atom via a divalent hydrocarbon group (i.e., a fluorinated organopolysiloxane-modified carboxylic anhydride compound) in one molecule can be used. As such a compound, a compound represented by the following general formula (15) can be exemplified. Furthermore, since the fluorinated organopolysiloxane-modified carboxylic anhydride compound has a molecular structure equivalent to that of a fluorinated organohydrogensiloxane, the use of the compound makes it difficult to maintain long-term self-adhesion to hydrofluoric acid and an electrolyte for a lithium ion secondary battery, but is extremely effective in the case of requiring initial self-adhesion in the manufacturing process of an article having a cured product obtained from the fluoropolyether-based curable composition of the present invention.

[0346] [Chemistry 70]

[0347]

[0348] (Where L 2 are independently a monovalent perfluoropolyether group bonded to a silicon atom via a divalent hydrocarbon group, J are independently a cyclic carboxylic acid anhydride residue bonded to a silicon atom via a divalent hydrocarbon group, R 8 are independently unsubstituted or halogen-substituted monovalent hydrocarbon groups, t2 is an integer of 1 to 6, u2 is an integer of 1 to 4, v2 is an integer of 1 to 4, and t2+u2+v2 is an integer of 4 to 10. The repeating units shown in the above () may be randomly bonded.)

[0349] In the above formula (15), L 2 is a monovalent perfluoropolyether group bonded to a silicon atom via a divalent hydrocarbon group, and examples thereof include 1 These are groups introduced from the viewpoints of compatibility with the component (A), dispersibility, and uniformity after curing.

[0350] In the above formula (15), R 8 is an unsubstituted or halogen-substituted monovalent hydrocarbon group, and examples thereof include the above-mentioned R 2 Among the same groups, methyl and ethyl are preferred.

[0351] In the above formula (15), J is a cyclic carboxylic acid anhydride residue bonded to a silicon atom via a divalent hydrocarbon group, and specifically, groups represented by the following general formula can be mentioned.

[0352] [Chemistry 71]

[0353]

[0354] In the above formula, R9 It is a divalent hydrocarbon group having 2 to 15 carbon atoms, and specific examples thereof include ethylene, propylene, and butylene. Among them, propylene is preferred.

[0355] Furthermore, in the above formula (15), t2 is an integer of 1 to 6, preferably an integer of 2 to 5, u2 is an integer of 1 to 4, preferably an integer of 1 to 3, v2 is an integer of 1 to 4, preferably an integer of 1 to 3, and t2+u2+v2 is an integer of 4 to 10, preferably an integer of 4 to 8. However, ((H)(R 8 )SiO) unit, ((L 2 )(R 8 )SiO) units and ((J)(R 8 The arrangement order of the )SiO) units is random.

[0356] Examples of the cyclic organopolysiloxane represented by the general formula (15) include the following compounds: In the following formula, Me represents a methyl group.

[0357] [Chemistry 72]

[0358]

[0359] (Wherein, t2'=2 or 3, b2'=integers from 2 to 20.)

[0360] [Chemistry 73]

[0361]

[0362] (wherein, v2'=2 or 3, b2'=2 to 20 integers.)

[0363] These adhesion promoters may be used alone or in combination of two or more. In this case, the carboxylic acid anhydride that is solid at 23° C. may be used in combination with the cyclic organopolysiloxane (fluorinated organopolysiloxane-modified carboxylic acid anhydride compound).

[0364] The amount of the adhesion promoter when mixed is preferably 0.01 to 2 parts by mass, more preferably 0.05 to 1 part by mass, relative to 100 parts by mass of component (A). In addition, the amount of the hydrosilyl group (Si-H group) in the adhesion promoter is preferably 0.005 to 0.5 mol, particularly preferably 0.05 to 0.1 mol, relative to 1 mol of the alkenyl group in component (A).

[0365] The total amount of the hydrosilyl groups contained in the composition (particularly the total amount of the hydrosilyl groups in the component (B), the adhesion improver and the adhesion promoter) is preferably 0.1 to 2.5 mol, particularly preferably 0.2 to 2 mol, per 1 mol of the alkenyl groups in the component (A).

[0366] [Method for producing fluoropolyether curable composition]

[0367] The method for producing the fluoropolyether curable composition of the present invention is not particularly limited, and the fluoropolyether curable composition can be produced by kneading the above components. Specifically, the fluoropolyether curable composition of the present invention can be produced by uniformly mixing the above components (A) to (D) and other optional components using a mixing device such as a planetary mixer, a Ross mixer, a Hobart mixer, and, if necessary, using a kneading device such as a kneader or a triple roll.

[0368] Alternatively, a two-component composition may be prepared and mixed when used.

[0369] The produced fluoropolyether curable composition may be cured at room temperature depending on the type of the catalyst of the component (C). In order to promote the curing, it may be heated. In particular, in order to stabilize the mechanical properties of the cured product, it is preferably cured at 60° C. or above, preferably 100 to 200° C., for a period of several minutes to several hours.

[0370] When the fluoropolyether curable composition of the present invention is used, the composition can be dissolved in a suitable fluorine-based solvent such as 1,3-bis(trifluoromethyl)benzene, Fluorinate (manufactured by 3M Co.), perfluorobutyl methyl ether, perfluorobutyl ethyl ether, etc. at a desired concentration and used according to its application and purpose. In particular, it is preferred to use the solvent for thin film coating applications.

[0371] The fluoropolyether curable composition of the present invention is preferably used as an electric or electronic component for automobiles, chemical equipment, semiconductor manufacturing lines, analytical physical and chemical equipment, residential environments, communication machinery, communication equipment, aircraft, rail vehicles, portable devices, power storage devices, robots, or lithium-ion batteries.

[0372] In particular, it is preferable to use a cured product of the fluoropolyether-based curable composition of the present invention as a gasket, a filler, a protective sealant or a coating layer in an electric or electronic component.

[0373] Example

[0374] Synthesis examples, embodiments and comparative examples are shown below to specifically illustrate the present invention, but the present invention is not limited to the following embodiments. It should be noted that parts in the following examples represent parts by mass. In addition, the number average molecular weight is determined using AK-225 (manufactured by Asahi Glass Co., Ltd.) as a fluorine-based solvent as an elution solvent and as a polystyrene-converted number average molecular weight in gel permeation chromatography (GPC) analysis. The viscosity is measured at 23°C using a rotational viscometer in the viscosity test specified in JIS K6249. The average particle size, unless otherwise specified, represents the value of the cumulative volume average diameter (D50) in the particle size distribution measurement using a laser diffraction scattering method.

[0375] Synthesis of fluorinated organohydrogensilane compounds

[0376] [Synthesis example 1]

[0377] In a 1 L flask, an organohydrogensilane compound represented by the following formula (16) (hydrogensilyl group content: 0.616 mol / 100 g) was placed.

[0378] [Chemistry 74]

[0379]

[0380] 150 g of a compound represented by the following formula (17) (vinyl group content: 0.0681 mol / 100 g)

[0381] [Chemistry 75]

[0382]

[0383] 339 g and 91 g of 1,3-bis(trifluoromethyl)benzene were added and the atmosphere was replaced with nitrogen.

[0384] After the temperature was raised to 70°C, 0.16 g of a toluene solution of (C1) platinum-divinyltetramethyldisiloxane complex (platinum concentration 0.5 mass%) was added dropwise, and the mixture was stirred at 85°C for 1 hour. The reaction solution was quenched and concentrated under reduced pressure. The obtained residue was dissolved in FC-3283 (524 g), stirred with 9.10 g of activated carbon (trade name Shirasagi AS, manufactured by Osaka Gas Chemical Co., Ltd.) for 1 hour, and filtered. Activated carbon (9.10 g) was added to the obtained solution, stirred for 1 hour, and then filtered.

[0385] The obtained solution was fractionated, the main component was extracted by chromatography, and then concentrated under reduced pressure to obtain a compound represented by the following formula (18) (hydrosilyl group content: 0.143 mol / 100 g):

[0386] [Chemistry 76]

[0387]

[0388] 376g. 1 In the H-NMR spectrum, the following signals were confirmed: δ7.86~6.55 (m, 4H), 4.38~3.64 (m, 3H), 3.15 (s, 3H), 2.46~1.48 (br, 4H), 1.18~-0.91 (m, 52H), confirming the formation of the compound represented by the above formula (18).

[0389] [Synthesis example 2]

[0390] Except that the compound represented by the following formula (19) (vinyl group content: 0.0228 mol / 100 g) was used instead of the compound represented by the above formula (17):

[0391] [Chemistry 77]

[0392]

[0393] Except for 1012 g, the same operation as in Synthesis Example 1 was carried out to obtain a compound represented by the following formula (20) (hydrosilyl group content: 0.0682 mol / 100 g):

[0394] [Chemistry 78]

[0395]

[0396] 741g. 1 In the H-NMR spectrum, the following signals were confirmed: δ7.68~6.36 (m, 4H), 4.21~3.44 (s, 3H), 3.03 (s, 3H), 2.29~1.41 (br, 4H), 1.13~-0.98 (m, 52H), confirming the formation of the compound represented by the above formula (20).

[0397] [Synthesis example 3]

[0398] Except that the compound represented by the following formula (21) (hydrosilyl group content: 1.09 mol / 100 g) was used instead of the compound represented by the above formula (16):

[0399] [Chemistry 79]

[0400]

[0401] Except for 85 g, the same operation as in Synthesis Example 1 was carried out to obtain a compound represented by the following formula (22) (hydrosilyl group content: 0.247 mol / 100 g):

[0402] [Chemistry 80]

[0403]

[0404] 323g. 1 In the H-NMR spectrum, the following signals were confirmed: δ7.85 to 6.55 (m, 4H), 4.29 to 3.51 (m, 5H), 3.15 (s, 3H), 1.23 to -0.91 (m, 62H), confirming the formation of the compound represented by the above formula (22).

[0405] [Synthesis Example 4]

[0406] Except that the compound represented by the following formula (23) (vinyl content: 0.0873 mol / 100 g) was used instead of the compound represented by the above formula (17):

[0407] [Chemistry 81]

[0408]

[0409] (average value of m+n = 12, m:n = 0.98:1)

[0410] Except for 264 g, the same operation as in Synthesis Example 1 was carried out to obtain a compound represented by the following formula (24) (hydrosilyl group content: 0.169 mol / 100 g):

[0411] [Chemistry 82]

[0412]

[0413] (average value of m+n = 12, m:n = 0.98:1)

[0414] 317g. 1 In the H-NMR spectrum, the following signals were confirmed: δ6.89~6.61 (s, 1H), 4.39~3.66 (m, 3H), 3.41~3.07 (m, 2H), 2.46~1.47 (br, 4H), 1.74~1.39 (m, 2H), 1.18~-0.90 (m, 44H), confirming the formation of the compound represented by the above formula (24).

[0415] [Synthesis example 5]

[0416] Except that the compound represented by the following formula (25) (vinyl group content: 0.0382 mol / 100 g) was used instead of the compound represented by the above formula (17):

[0417] [Chemistry 83]

[0418]

[0419] Except for 605 g, the same operation as in Synthesis Example 1 was carried out to obtain a compound represented by the following formula (26) (hydrosilyl group content: 0.0872 mol / 100 g):

[0420] [Chemistry 84]

[0421]

[0422] 502g. 1 In the H-NMR spectrum, the following signals were confirmed: δ4.39 to 3.66 (m, 5H), 3.59 to 3.30 (s, 2H), 2.46 to 1.47 (m, 6H), 1.18 to -0.90 (m, 44H), confirming the formation of the compound represented by the above formula (26).

[0423] [Synthesis example 6]

[0424] Except that the compound represented by the following formula (27) (vinyl group content: 0.0531 mol / 100 g) was used instead of the compound represented by the above formula (17):

[0425] [Chemistry 85]

[0426]

[0427] Except for 435 g, the same operation as in Synthesis Example 1 was carried out to obtain a compound represented by the following formula (28) (hydrosilyl group content: 0.112 mol / 100 g):

[0428] [Chemistry 86]

[0429]

[0430] 446g. 1 In the H-NMR spectrum, the following signals were confirmed: δ4.41 to 3.64 (m, 5H), 3.59 to 3.29 (s, 2H), 2.46 to 1.47 (m, 6H), 1.18 to -0.90 (m, 44H), confirming the formation of the compound represented by the above formula (28).

[0431] [Synthesis Example 7]

[0432] Except that the compound represented by the following formula (29) (vinyl content: 0.0531 mol / 100 g) was used instead of the compound represented by the above formula (17):

[0433] [Chemistry 87]

[0434]

[0435] Except for 435 g, the same operation as in Synthesis Example 1 was carried out to obtain a compound represented by the following formula (30) (hydrosilyl group content: 0.112 mol / 100 g):

[0436] [Chemistry 88]

[0437]

[0438] 438g. 1 In the H-NMR spectrum, the following signals were confirmed: δ4.41 to 3.64 (m, 5H), 3.59 to 3.29 (s, 2H), 2.46 to 1.47 (m, 6H), 1.18 to -0.90 (m, 44H), confirming the formation of the compound represented by the above formula (30).

[0439] <Preparation of Fluoropolyether Curable Composition, Confirmation of Compatibility between Component (B) and Component (A) (Base Oil)>

[0440] [Reference Example 1]

[0441] 0.1 part of a toluene solution of a platinum-divinyltetramethyldisiloxane complex (platinum concentration 0.5 mass%), 0.07 part of a compound represented by the following formula (32), and 9.74 parts of a compound represented by the following formula (18) obtained in Synthesis Example 1 (hydrogen silyl group content 0.143 mol / 100 g) were added to 100 parts of a polymer (A1) represented by the following formula (31) (number average molecular weight 15550, viscosity 10900 mPa·s, vinyl group content 0.012 mol / 100 g), and mixed to prepare a curable composition, which was obtained as a transparent oil. This shows that the compatibility of the component (B1) and the component (A1) is high. In the formula, Me represents a methyl group.

[0442] [Chemistry 89]

[0443]

[0444] (In the formula, m and n are integers greater than 1, and the average value of m+n=90.)

[0445] [Chemistry 90]

[0446]

[0447] [Chemistry 91]

[0448]

[0449] [Reference Example 2]

[0450] In Reference Example 1, 100 parts of a polymer (number average molecular weight 15630, viscosity 11000 mPa·s, vinyl content 0.012 mol / 100 g) represented by the following formula (33) were used instead of the polymer (A1) represented by the above formula (31). A curable composition was prepared in the same manner as in Reference Example 1 to obtain a transparent oil. This shows that the compatibility of the component (B1) and the component (A2) is high. In the formula, Me represents a methyl group.

[0451] [Chemistry 92]

[0452]

[0453] (In the formula, m and n are integers greater than 1, and the average value of m+n=90.)

[0454] [Reference Example 3]

[0455] In Reference Example 1, a curable composition was prepared in the same manner as in Reference Example 1, except that 100 parts of a polymer (number average molecular weight 3350, viscosity 60 mPa·s, vinyl content 0.031 mol / 100 g) represented by the following formula (34) (A3) and 25.16 parts of a compound represented by the above formula (18) (B1) were used instead of the polymer represented by the above formula (31). This showed that the compatibility of the component (B1) and the component (A3) was high.

[0456] [Chemistry 93]

[0457] CH2=CH-CH2-O-CH2-CF2-(OC2F4) n -(OCF2) m -O-CF2-CH2-O-CH2-CH=CH2 (34)

[0459] (m:n=0.98:1, average value of m+n=34)

[0460] [Reference Example 4]

[0461] In Reference Example 1, 20.42 parts of the compound represented by the following formula (20) obtained in Synthesis Example 2 (hydrosilyl group amount: 0.0682 mol / 100 g) were used instead of the compound represented by the above formula (18) (B1) in Reference Example 1. A curable composition was prepared in the same manner as in Reference Example 1 to obtain a transparent oil. This indicates that the compatibility of the component (B2) and the component (A1) is high. In the formula, Me represents a methyl group.

[0462] [Chemistry 94]

[0463]

[0464] [Reference Example 5]

[0465] In Reference Example 1, 5.73 parts of the compound represented by the following formula (22) obtained in Synthesis Example 3 (hydrosilyl group amount: 0.247 mol / 100 g) were used instead of the compound represented by the above formula (18) (B1) in the same manner as in Reference Example 1 to prepare a curable composition, and a transparent oil was obtained. This shows that the compatibility of the component (B3) and the component (A1) is high. In the formula, Me represents a methyl group.

[0466] [Chemistry 95]

[0467]

[0468] [Reference Example 6]

[0469] In Reference Example 1, 8.24 parts of the compound represented by the following formula (24) obtained in Synthesis Example 4 (hydrosilyl group amount: 0.169 mol / 100 g) were used instead of the compound represented by the above formula (18) (B1) in the same manner as in Reference Example 1 to prepare a curable composition, which was obtained as a transparent oil. This shows that the compatibility of the component (B4) and the component (A1) is high. In the formula, Me represents a methyl group.

[0470] [Chemistry 96]

[0471]

[0472] (m:n=0.98:1, average value of m+n=12)

[0473] [Reference Example 7]

[0474] In Reference Example 1, 9.61 parts of a mixture of (B5) a compound represented by the above formula (18) obtained in the same manner as in Reference Example 1 and compounds represented by the following formulas (35), (36), (37) and (38) (mass ratio: (18) / (35) / (36) / (37) / (38) = 80:9:6:1:4, amount of hydrosilyl group: 0.145 mol / 100 g) were used instead of (B1) a compound represented by the above formula (18), and a clear oil was obtained. This shows that the compatibility of the component (B5) with the component (A1) is high. In the formula, Me represents a methyl group.

[0475] [Chemistry 97]

[0476]

[0477] [Reference Example 8]

[0478] In Reference Example 1, 15.97 parts of the compound represented by the following formula (26) obtained in Synthesis Example 5 (hydrosilyl group amount: 0.0872 mol / 100 g) were used instead of the compound represented by the above formula (18) (B1) in the reference example 1. The curable composition was prepared in the same manner as in Reference Example 1, and a transparent oil was obtained. This shows that the compatibility of the component (B6) and the component (A1) is high. In the formula, Me represents a methyl group.

[0479] [Chemistry 98]

[0480]

[0481] [Reference Example 9]

[0482] In Reference Example 1, 12.44 parts of the compound represented by the following formula (28) obtained in Synthesis Example 6 (hydrosilyl group amount: 0.112 mol / 100 g) (B7) were used instead of the compound represented by the above formula (18) in Reference Example 1. A curable composition was prepared in the same manner as in Reference Example 1 to obtain a transparent oil. This indicates that the compatibility of the component (B7) and the component (A1) is high. In the formula, Me represents a methyl group.

[0483] [Chemistry 99]

[0484]

[0485] [Reference Example 10]

[0486] In Reference Example 1, 12.44 parts of the compound represented by the following formula (30) obtained in Synthesis Example 7 (hydrosilyl group amount: 0.112 mol / 100 g) were used instead of the compound represented by the above formula (18) (B8). A curable composition was prepared in the same manner as in Reference Example 1 to obtain a transparent oil. This indicates that the compatibility of the component (B8) and the component (A1) is high. In the formula, Me represents a methyl group.

[0487] [Chemical 100]

[0488]

[0489] [Comparative Example 1]

[0490] In Reference Example 1, except that 2.26 parts of the compound (B9) represented by the above formula (16) (hydrosilyl group amount: 0.616 mol / 100 g) was used instead of the compound (B1) represented by the above formula (18), a curable composition was prepared in the same manner as in Reference Example 1 to obtain a turbid oil. This indicates that the compatibility of the component (B9) with the component (A1) is low.

[0491] [Comparative Example 2]

[0492] In Reference Example 1, 3.52 parts of a compound represented by the following formula (39) (Patent Document 5: Compound described in Example 1 of Japanese Patent Application Laid-Open No. 2002-012769, amount of hydrosilyl group: 0.408 mol / 100 g) (B10) were used instead of the compound represented by the above formula (18). A curable composition was prepared in the same manner as in Reference Example 1, and a slightly turbid oil was obtained. This indicates that the compatibility of the component (B10) with the component (A1) is low. In the formula, Me represents a methyl group.

[0493] [Chemistry 101]

[0494]

[0495] [Comparative Example 3]

[0496] In Reference Example 1, a curable composition was prepared in the same manner as in Reference Example 1 except that 3.54 parts of a compound (B11) represented by the following formula (40) (hydrosilyl group amount: 0.394 mol / 100 g) was used instead of the compound (B1) represented by the above formula (18), and a transparent oil was obtained. This shows that the compatibility of the component (B11) and the component (A1) is high. In the formula, Me represents a methyl group.

[0497] [Chemistry 102]

[0498]

[0499] <Confirmation of the presence of oily components (uncured parts) on the surface of fluoropolyether-based cured products and evaluation of the mold release properties of cured products>

[0500] The fluoropolyether curable compositions prepared in Reference Examples 1 to 10 and Comparative Examples 1 to 3 were cast in a 2 mm thick stainless steel mold placed on a sheet made of Teflon (registered trademark, the same below), clamped with another Teflon sheet, and press-cured at 150°C / 10 minutes. After press-curing, the remaining oily component on the surface of the fluoropolyether cured product obtained by removing the 2 mm thick stainless steel mold was evaluated using the following evaluation criteria. The results are shown in Table 1.

[0501] [Evaluation criteria]

[0502] ◯: The cured product can be easily peeled off from the Teflon sheet without being damaged, and no oily component is observed to remain on the surface of the peeled cured product.

[0503] ×: It was difficult to peel the cured product from the Teflon sheet without damaging it, and oily components remained on the surface of the peeled cured product.

[0504] [Table 1]

[0505] Appearance of fluoropolyether curable composition Presence of oily ingredients and mold release properties Reference Example 1 transparent ○ Reference Example 2 transparent ○ Reference Example 3 transparent ○ Reference Example 4 transparent ○ Reference Example 5 transparent ○ Reference Example 6 transparent ○ Reference Example 7 transparent ○ Reference Example 8 transparent ○ Reference Example 9 transparent ○ Reference Example 10 transparent ○ Comparative Example 1 White turbidity × Comparative Example 2 Slightly turbid × Comparative Example 3 transparent ○

[0506] In the case of the fluoropolyether cured products obtained from the fluoropolyether cured compositions of Reference Examples 1 to 10 and Comparative Example 3, no uncured oily components were observed to be dispersed on the surface of the cured products. This is because, since the (B) component contained in the fluoropolyether cured compositions of Reference Examples 1 to 10 and Comparative Example 3 showed high compatibility with the (A) component, almost all of the (B) component reacted with the (A) component. In addition, since the cured product could be easily peeled off from the Teflon sheet even after pressurized curing, it was confirmed that there was no problem with demolding. On the other hand, uncured oily components were observed to be dispersed on the surface of the fluoropolyether cured products obtained from the fluoropolyether cured compositions of Comparative Examples 1 and 2. It is believed that this is because the (B6) and (B7) components lacked compatibility with the (A) component, and the reaction with the (A) component became insufficient during thermal curing, so that the unreacted products remained on the surface of the fluoropolyether cured products as oily components. Furthermore, pressure curing was adopted, and as a result, the cured product was fixed to the Teflon sheet, and the mold release property was also low, such as the cured product being broken or chipped when peeled from the Teflon sheet.

[0507] The fluoropolyether-based cured product obtained above was post-cured at 200° C. for 4 hours, and then evaluated for heat resistance, chemical resistance, solvent resistance, and electrolyte resistance as shown below. The results are shown in Tables 2 to 5.

[0508] <Heat resistance>

[0509] The physical properties of the fluoropolyether cured products obtained from the fluoropolyether curable compositions of Reference Examples 1 to 10 and Comparative Examples 1 to 3 were evaluated according to JIS K 6249. Next, the fluoropolyether cured products obtained from the fluoropolyether curable compositions of Reference Examples 1 to 10 and Comparative Examples 1 to 3 were placed in an oven at 150° C. for 7 days, and the physical properties of the cured products were evaluated according to JIS K 6249, and the hardness change, tensile strength change rate (%), and elongation at break change rate (%) were calculated using the following calculation formulas. The results are shown in Table 2.

[0510] Hardness change = (hardness of cured product after 150°C / 7 days) - (initial hardness of cured product)

[0511] Tensile strength change rate (%) = ((tensile strength of the cured product after 150°C / 7 days) - (tensile strength of the cured product at the initial stage)) / (tensile strength of the cured product at the initial stage) × 100 Elongation at break change rate (%) = ((elongation at break of the cured product after 150°C / 7 days) - (elongation at break of the cured product at the initial stage)) / (elongation at break of the cured product at the initial stage) × 100

[0512] [Table 2]

[0513]

[0514] <Chemical resistance>

[0515] The fluoropolyether cured products obtained from the fluoropolyether curable compositions of Reference Examples 1 to 10 and Comparative Examples 1 to 3 were immersed in concentrated hydrochloric acid, concentrated sulfuric acid, concentrated hydrofluoric acid, trifluoroacetic acid, and 40 mass% KOH (potassium hydroxide) aqueous solution at 20°C for 3 days, and the change in hardness was measured based on the hardness before immersion. The change in hardness was calculated using the same mathematical formula as in the heat resistance test. The results are shown in Table 3.

[0516] [Table 3]

[0517]

[0518] The results in Table 3 show that the fluoropolyether cured products obtained from the fluoropolyether curable compositions of Reference Examples 1 to 10 and Comparative Examples 1 and 2 have excellent durability against all of the above chemicals. On the other hand, it was confirmed that the fluoropolyether cured product obtained from the fluoropolyether curable composition of Comparative Example 3 lacked durability against concentrated hydrofluoric acid and trifluoroacetic acid.

[0519] <Solvent resistance>

[0520] Using the fluoropolyether-based cured products obtained from the fluoropolyether-based curable compositions of Reference Examples 1 to 10 and Comparative Examples 1 to 3, immersion tests in various organic solvents shown in Table 4 were carried out in accordance with JIS K 6258 (immersion time: 70 hours), and the volume change rate (%) before and after immersion was measured to evaluate the resistance to solvent swelling. The results are shown in Table 4.

[0521] [Table 4]

[0522]

[0523] *1) IPA: Isopropyl alcohol

[0524] *2) MEK: Methyl Ethyl Ketone

[0525] *3)THF: Tetrahydrofuran

[0526] From the results in Table 4, it was confirmed that the fluoropolyether cured products obtained from the fluoropolyether curable compositions of Reference Examples 1 to 10, like the fluoropolyether cured products obtained from the curable fluoropolyether curable compositions of Comparative Examples 1 to 3, had excellent durability against all the above solvents.

[0527] <Electrolyte resistance>

[0528] The fluoropolyether-based cured products obtained from the fluoropolyether-based curable compositions of Reference Examples 1 to 10 and Comparative Examples 1 to 3 were immersed in an electrolyte for lithium ion batteries (manufactured by Kishida Chemical Co., Ltd.) at 80° C. for 3 days, and the degree of degradation of the cured products was evaluated based on changes in hardness, stickiness, and appearance of the cured products before and after the immersion using the following evaluation criteria.

[0529] [Evaluation criteria]

[0530] [hardness]

[0531] ○: Almost no change in hardness was observed before and after immersion in the lithium ion battery electrolyte.

[0532] ×: A significant decrease in hardness was observed due to the impregnation with the lithium-ion battery electrolyte.

[0533] [Sticky]

[0534] ○: There is no change in stickiness of the cured product surface due to immersion in the lithium ion battery electrolyte solution.

[0535] ×: The surface of the cured product became sticky due to the impregnation with the lithium ion battery electrolyte.

[0536] [Changes in appearance]

[0537] ○: Almost no change in appearance was observed before and after immersion in the lithium ion battery electrolyte.

[0538] ×: Due to the immersion in the lithium-ion battery electrolyte, swelling, deformation, and decomposition of the solidified material were observed.

[0539] [Table 5]

[0540]

[0541] As for the fluoropolyether cured products obtained from the fluoropolyether cured compositions of Reference Examples 1 to 10 and Comparative Examples 1 and 2, almost no changes were found in hardness, surface stickiness, and appearance before and after immersion in the electrolyte for lithium ion batteries. It can be seen that the above-mentioned compositions and cured products can be applied to lithium ion batteries. On the other hand, as for the fluoropolyether cured product obtained from the fluoropolyether cured composition of Comparative Example 3, changes such as swelling and surface decomposition due to immersion in the electrolyte for lithium ion batteries were confirmed. In addition, if both ends of the cured product are stretched, it is simply broken.

[0542] <Preparation of filler-containing fluoropolyether curable composition>

[0543] [Example 1]

[0544] First, 100 parts of the polymer (A1) represented by the above formula (31) and 30 parts of the polyimide resin powder (manufactured by Ebonic Co., Ltd., spherical, average particle size: 9.2 μm) (D1) were kneaded at room temperature for 1 hour using a planetary mixer, and then kneaded at room temperature under a reduced pressure of -98.0 kPaG for 1 hour. Furthermore, the mixture was kneaded at 150°C under a reduced pressure of -98.0 kPaG for 1 hour. Secondly, after the mixture was cooled to room temperature, it was treated with a triple roll mill. 0.1 parts of a toluene solution of a platinum-divinyltetramethyldisiloxane complex (platinum concentration 0.5 mass%), 0.07 parts of a compound represented by the above formula (32), and 9.74 parts of a compound represented by the above formula (18) obtained in (B1) Synthesis Example 1 were added to the mixture, and mixed to prepare a curable composition.

[0545] [Example 2]

[0546] In Example 1, a curable composition was prepared in the same manner as in Example 1 except that 100 parts of the polymer (A2) represented by the above formula (33) was used instead of the polymer (A1) represented by the above formula (31).

[0547] [Example 3]

[0548] In Example 1, a curable composition was prepared in the same manner as in Example 1 except that 100 parts of the polymer represented by the above formula (34) (A3) and 25.16 parts of the compound represented by the above formula (18) (B1) were used instead of the polymer represented by the above formula (31) (A1).

[0549] [Example 4]

[0550] In Example 1, a curable composition was prepared in the same manner as in Example 1 except that (B2) 20.42 parts of the compound represented by the above formula (20) obtained in Synthesis Example 2 was used instead of (B1) the compound represented by the above formula (18).

[0551] [Example 5]

[0552] In Example 1, a curable composition was prepared in the same manner as in Example 1 except that (B3) 5.73 parts of the compound represented by the above formula (22) obtained in Synthesis Example 3 was used instead of (B1) the compound represented by the above formula (18).

[0553] [Example 6]

[0554] In Example 1, a curable composition was prepared in the same manner as in Example 1 except that 8.24 parts of the compound represented by the above formula (24) obtained in Synthesis Example 4 (B4) was used instead of the compound represented by the above formula (18) (B1).

[0555] [Example 7]

[0556] In Example 1, a curable composition was prepared in the same manner as in Example 1 except that 9.61 parts of a mixture of compounds represented by the above formulae (18), (35), (36), (37) and (38) (B5) obtained in the same manner as in Synthesis Example 1 was used instead of the compound represented by the above formula (18) (B1).

[0557] [Example 8]

[0558] In Example 1, a curable composition was prepared in the same manner as in Example 1 except that 15.97 parts of the compound represented by the above formula (26) obtained in Synthesis Example 5 (B6) was used instead of the compound represented by the above formula (18) (B1).

[0559] [Example 9]

[0560] In Example 1, a curable composition was prepared in the same manner as in Example 1 except that 12.44 parts of the compound represented by the above formula (28) obtained in Synthesis Example 5 (B7) was used instead of the compound represented by the above formula (18) (B1).

[0561] [Example 10]

[0562] In Example 1, a curable composition was prepared in the same manner as in Example 1 except that 12.44 parts of the compound represented by the above formula (30) obtained in Synthesis Example 5 (B8) was used instead of the compound represented by the above formula (18) (B1).

[0563] [Example 11]

[0564] In Example 7, a curable composition was prepared in the same manner as in Example 7 except that 100 parts of the polymer (A2) represented by the above formula (33) was used instead of the polymer (A1) represented by the above formula (31).

[0565] [Example 12]

[0566] In Example 1, a curable composition was prepared in the same manner as in Example 1 except that 40 parts of the polyimide resin powder (D1) was used.

[0567] [Example 13]

[0568] In Example 12, a curable composition was prepared in the same manner as in Example 12 except that 100 parts of the polymer (A2) represented by the above formula (33) was used instead of the polymer (A1) represented by the above formula (31).

[0569] [Example 14]

[0570] In Example 1, a curable composition was prepared in the same manner as in Example 1 except that 60 parts of the polyimide resin powder (D1) was used.

[0571] [Example 15]

[0572] In Example 1, a curable composition was prepared in the same manner as in Example 1 except that 10 parts of acetylene black carbon powder (D2) (granular product manufactured by DENKA Corporation, average particle size 0.035 μm) was used instead of the polyimide resin powder (D1).

[0573] [Example 16]

[0574] In Example 15, a curable composition was prepared in the same manner as in Example 15 except that 100 parts of the polymer (A2) represented by the above formula (33) was used instead of the polymer (A1) represented by the above formula (31).

[0575] [Example 17]

[0576] In Example 1, a curable composition was prepared in the same manner as in Example 1 except that 10 parts of acetylene black carbon powder (D3, manufactured by DENKA Corporation, powdered product, average particle size 0.035 μm) was used instead of the polyimide resin powder (D1).

[0577] [Example 18]

[0578] In Example 17, a curable composition was prepared in the same manner as in Example 17 except that 100 parts of the polymer (A2) represented by the above formula (33) was used instead of the polymer (A1) represented by the above formula (31).

[0579] [Example 19]

[0580] In Example 1, a curable composition was prepared in the same manner as in Example 1 except that 10 parts of acetylene black carbon powder (D2) (granular product manufactured by DENKA Corporation, average particle size 0.035 μm) was used in addition to the polyimide resin powder (D1).

[0581] [Comparative Example 4]

[0582] In Example 1, a curable composition was prepared in the same manner as in Example 1 except that 23.0 parts of fumed silica (Aerosil R-972, manufactured by AEROSIL Corporation, average particle size (catalog value): 16 nm) was used instead of the polyimide resin powder (D1).

[0583] <Evaluation of fluoropolyether-based cured products containing fillers>

[0584] The fluoropolyether curable compositions prepared in Reference Examples 1 to 3, Examples 1 to 19, and Comparative Example 4 were cast in a 2 mm thick stainless steel mold placed on a Teflon sheet, sandwiched with another Teflon sheet, and press-cured at 150°C for 10 minutes. After press-curing, the fluoropolyether cured product obtained by removing the 2 mm thick stainless steel mold was post-cured at 200°C for 4 hours, and the heat resistance, chemical resistance, solvent resistance, and electrolyte resistance shown below were evaluated. The results are shown in Tables 6 to 13.

[0585] <Heat resistance>

[0586] The physical properties of the fluoropolyether-based cured products obtained from the fluoropolyether-based curable compositions of Reference Examples 1 to 3, Examples 1 to 19, and Comparative Example 4 were evaluated in accordance with JIS K 6249. The results are shown in Table 6.

[0587] [Table 6]

[0588]

[0589] Next, each fluoropolyether-based cured product (Examples 1 to 19, Comparative Example 4) was placed in an oven at 150°C for 7 days, and the physical properties of the cured product were evaluated according to JIS K 6249, and the hardness change, tensile strength change rate (%), and elongation at break change rate (%) were calculated using the following calculation formula. The results are shown in Table 7.

[0590] Hardness change = (hardness of cured product after 150°C / 7 days) - (initial hardness of cured product)

[0591] Tensile strength change rate (%) = ((tensile strength of the cured product after 150°C / 7 days) - (tensile strength of the cured product at the initial stage)) / (tensile strength of the cured product at the initial stage) × 100 Elongation at break change rate (%) = ((elongation at break of the cured product after 150°C / 7 days) - (elongation at break of the cured product at the initial stage)) / (elongation at break of the cured product at the initial stage) × 100

[0592] [Table 7]

[0593]

[0594] From the results in Table 6, it was confirmed that the mechanical properties, particularly hardness and tensile strength, of the fluoropolyether-based cured products obtained from the fluoropolyether-based curable compositions of Examples 1 to 19 containing at least one filler selected from organic resin powder and carbon black powder were superior to those of the fluoropolyether-based cured products obtained from the fluoropolyether-based curable compositions of Reference Examples 1 to 3 not containing organic resin powder and carbon black powder were superior. Furthermore, from the results in Table 7, it was confirmed that the fluoropolyether-based cured products obtained from the fluoropolyether-based curable compositions of Examples 1 to 19 to which at least one filler selected from organic resin powder and carbon black powder was added had heat resistance at the same level as that of the fluoropolyether-based cured product obtained from the fluoropolyether-based curable composition of Comparative Example 4 reinforced with fumed silica.

[0595] <Chemical resistance>

[0596] The fluoropolyether cured products obtained from the fluoropolyether curable compositions of Examples 1 to 19 and Comparative Example 4 were immersed in concentrated hydrochloric acid, concentrated sulfuric acid, concentrated hydrofluoric acid, and trifluoroacetic acid at 20°C for 3 days, and the change in hardness was measured based on the hardness before immersion. The change in hardness was calculated using the same mathematical formula as in the heat resistance test. The results are shown in Tables 8 and 9.

[0597] [Table 8]

[0598]

[0599] [Table 9]

[0600]

[0601] From the results in Tables 8 and 9, it was confirmed that the fluoropolyether cured products obtained from the fluoropolyether curable compositions of Examples 1 to 19 had durability against all of the above chemicals at the same level as that of the fluoropolyether cured products obtained from the fluoropolyether curable compositions of Reference Examples 1 to 10. On the other hand, it was confirmed that the fluoropolyether cured product obtained from the fluoropolyether curable composition of Comparative Example 4 lacked durability against concentrated hydrofluoric acid and trifluoroacetic acid.

[0602] <Solvent resistance>

[0603] Using the fluoropolyether-based cured products obtained from the fluoropolyether-based curable compositions of Examples 1 to 19 and Comparative Example 4, immersion tests were performed in various organic solvents shown in Table 4 (immersion time: 70 hours) in accordance with JIS K 6258, and the volume change rate (%) before and after immersion was measured to evaluate the resistance to solvent swelling. The results are shown in Tables 10 and 11.

[0604] [Table 10]

[0605]

[0606] *1) IPA: Isopropyl alcohol

[0607] *2) MEK: Methyl Ethyl Ketone

[0608] *3)THF: Tetrahydrofuran

[0609] [Table 11]

[0610]

[0611] *1) IPA: Isopropyl alcohol

[0612] *2) MEK: Methyl Ethyl Ketone

[0613] *3)THF: Tetrahydrofuran

[0614] The results in Tables 10 and 11 show that the fluoropolyether cured products obtained from the fluoropolyether curable compositions of Examples 1 to 19 have excellent durability against all of the above solvents, similarly to the fluoropolyether cured product obtained from the fluoropolyether curable composition of Comparative Example 4. The above results show that the addition of at least one filler selected from organic resin powders and carbon black powders has little effect on the solvent resistance of the fluoropolyether curable composition.

[0615] <Electrolyte resistance>

[0616] The fluoropolyether-based cured products obtained from the fluoropolyether-based curable compositions of Examples 1 to 19 and Comparative Example 4 were immersed in an electrolyte for lithium ion batteries (manufactured by Kishida Chemical Co., Ltd.) at 80°C for 3 days, and the degree of degradation of the cured products was evaluated based on the changes in hardness, stickiness, and appearance of the cured products before and after the immersion using the following evaluation criteria. The results are shown in Tables 12 and 13.

[0617] [Evaluation criteria]

[0618] [hardness]

[0619] ○: Almost no change in hardness was observed before and after immersion in the lithium ion battery electrolyte.

[0620] ×: A significant decrease in hardness was observed due to the impregnation with the lithium-ion battery electrolyte.

[0621] [Sticky]

[0622] ○: There is no change in stickiness of the cured product surface due to immersion in the lithium ion battery electrolyte solution.

[0623] ×: The surface of the cured product became sticky due to the impregnation with the lithium ion battery electrolyte.

[0624] [Changes in appearance]

[0625] ○: Almost no change in appearance was observed before and after immersion in the lithium ion battery electrolyte.

[0626] ×: Due to the immersion in the lithium-ion battery electrolyte, swelling, deformation, and decomposition of the solidified material were observed.

[0627] [Table 12]

[0628]

[0629] [Table 13]

[0630]

[0631] As for the fluoropolyether cured products obtained from the fluoropolyether cured compositions of Examples 1 to 19, almost no changes were found in hardness, surface stickiness, and appearance before and after immersion in the electrolyte for lithium ion batteries. It can be seen that the above-mentioned composition and cured product containing at least one filler selected from organic resin powder and carbon black powder can be applied to lithium ion battery applications. On the other hand, as for the fluoropolyether cured product obtained from the fluoropolyether cured composition of Comparative Example 4, although almost no stickiness or changes in appearance were found due to immersion in the electrolyte for lithium ion batteries, a significant reduction in hardness was confirmed. In addition, if the two ends of the cured product are stretched, it is simply broken, and the result showing the reduction of the mechanical and physical properties of the cured product is obtained.

[0632] <Preparation of a fluoropolyether curable composition containing a pulverized filler>

[0633] The polyimide resin powder (D1) was pulverized by a jet mill to prepare three types of polyimide resin powders each having an average particle size of 2.0 μm (D5), 3.0 μm (D6), and 5.0 μm (D7). Using these polyimide resin powders, the preparation of a fluoropolyether-based curable composition was attempted.

[0634] [Example 20]

[0635] First, 100 parts of the polymer (A1) represented by the above formula (31) and 70 parts of the polyimide resin powder (D5) (average particle size: 2.0 μm) were kneaded at room temperature for 1 hour using a planetary mixer, and then kneaded at room temperature under a reduced pressure of -98.0 kPaG for 1 hour. Furthermore, the mixture was kneaded at 150°C under a reduced pressure of -98.0 kPaG for 1 hour. As a result, a paste-like kneaded product was obtained. Secondly, the kneaded product was cooled to room temperature, treated with a triple roll mill, and then 0.1 parts of a toluene solution of a platinum-divinyltetramethyldisiloxane complex (platinum concentration 0.5 mass%), 0.07 parts of a compound represented by the above formula (32), and 9.74 parts of a compound represented by the above formula (18) obtained in (B1) Synthesis Example 1 were added and mixed to prepare a curable composition.

[0636] [Example 21]

[0637] In Example 20, a curable composition was prepared in the same manner as in Example 20 except that 100 parts of the polyimide resin powder (D5) (average particle size: 2.0 μm) was used.

[0638] [Example 22]

[0639] In Example 20, a curable composition was prepared in the same manner as in Example 20 except that 70 parts of the polyimide resin powder (D6) (average particle size 3.0 μm) was used instead of the polyimide resin powder (D5) (average particle size: 2.0 μm).

[0640] [Example 23]

[0641] In Example 22, a curable composition was prepared in the same manner as in Example 22 except that 100 parts of the polyimide resin powder (D6) (average particle size: 3.0 μm) was used.

[0642] [Example 24]

[0643] In Example 20, a curable composition was prepared in the same manner as in Example 20 except that 70 parts of the polyimide resin powder (D7) (average particle size 5.0 μm) was used instead of the polyimide resin powder (D5) (average particle size: 2.0 μm).

[0644] [Example 25]

[0645] In Example 20, a curable composition was prepared in the same manner as in Example 20 except that 100 parts of the polymer (A2) represented by the above formula (33) was used instead of the polymer (A1) represented by the above formula (31).

[0646] [Example 26]

[0647] In Example 21, a curable composition was prepared in the same manner as in Example 21 except that 100 parts of the polymer (A2) represented by the above formula (33) was used instead of the polymer (A1) represented by the above formula (31).

[0648] [Example 27]

[0649] In Example 22, a curable composition was prepared in the same manner as in Example 22 except that 100 parts of the polymer (A2) represented by the above formula (33) was used instead of the polymer (A1) represented by the above formula (31).

[0650] [Example 28]

[0651] In Example 23, a curable composition was prepared in the same manner as in Example 23 except that 100 parts of the polymer (A2) represented by the above formula (33) was used instead of the polymer (A1) represented by the above formula (31).

[0652] [Example 29]

[0653] In Example 24, a curable composition was prepared in the same manner as in Example 24 except that 100 parts of the polymer (A2) represented by the above formula (33) was used instead of the polymer (A1) represented by the above formula (31).

[0654] [Example 30]

[0655] In Example 20, a curable composition was prepared in the same manner as in Example 20 except that 100 parts of the polymer (A3) represented by the above formula (34) was used instead of the polymer (A1) represented by the above formula (31).

[0656] <Evaluation of Fluoropolyether Cured Products Containing Pulverized Fillers>

[0657] The fluoropolyether curable compositions prepared in Examples 20 to 30 were cast in a 2 mm thick stainless steel mold placed on a Teflon sheet, sandwiched with another Teflon sheet, and press-cured at 150° C. for 10 minutes. After press-curing, the 2 mm thick stainless steel mold was removed to obtain a fluoropolyether cured product, which was post-cured at 200° C. for 4 hours.

[0658] The physical properties of the fluoropolyether cured products obtained from the fluoropolyether curable compositions of Examples 20 to 30 were evaluated in accordance with JIS K 6249. The results are shown in Table 14 together with the results of Examples 1 to 3, 12, and 13 described above.

[0659] [Table 14]

[0660]

[0661] ※The values ​​in () indicate the filling amount (parts by mass)

[0662] From the results in Table 14, it can be seen that the hardness and tensile strength of the fluoropolyether-based cured products obtained from the fluoropolyether-based curable compositions of Examples 20 to 30 using the polyimide resin powders of (D5), (D6) and (D7) subjected to the pulverization treatment are improved compared to the fluoropolyether-based cured products obtained from the fluoropolyether-based curable compositions of Examples 1 to 3, 12 and 13 using the polyimide resin powders of (D1) that have not been subjected to the pulverization treatment. From the above results, it can be confirmed that the reinforcing effect of the cured product by filling a large amount of organic resin powder is achieved.

[0663] In addition, the fluoropolyether cured products obtained from the fluoropolyether curing compositions of Examples 20 to 30 were evaluated for heat resistance, chemical resistance, solvent resistance, and electrolyte resistance in the same manner as in Examples 1 to 19. The results of heat resistance, chemical resistance, solvent resistance, and electrolyte resistance were generally consistent with those of Examples 1 to 3, 12, and 13, confirming that there was no adverse effect caused by pulverizing the organic resin powder.

[0664] As can be seen from the above, the fluoropolyether cured product obtained from the fluoropolyether curable composition of the present invention has both durability and demoulding properties for hydrofluoric acid and lithium ion battery electrolyte. It can be further seen that by adding at least one filler selected from organic resin powder and carbon black powder, the mechanical physical properties are improved without damaging the characteristics of the cured product. It can be further seen that by pulverizing the organic resin powder, the average particle size is reduced, so that the filling amount in the fluoropolyether curable composition can be increased, thereby obtaining a further reinforced fluoropolyether cured product. The above content shows the effect of the present invention.

Claims

1. A fluoropolyether curable composition comprising: (A) a perfluoropolyether compound having two or more alkenyl groups in one molecule: 100 parts by mass, (B) a fluorinated organohydrogensilane compound represented by the following general formula (1) and having two or more hydrosilyl groups, in an amount such that the number of hydrogen atoms bonded to silicon atoms in the component (B) is 0.1 to 2.5 mol per 1 mol of alkenyl groups in the component (A); [Chemistry 1] In the formula, Rf is a monovalent perfluoropolyether group, A is a divalent organic group having 1 to 20 carbon atoms which may contain at least one selected from an oxygen atom, a nitrogen atom and a silicon atom, R is independently a monovalent hydrocarbon group having 1 to 6 carbon atoms, x is an integer of 1 to 3, B is independently a monovalent organic group having one or more diorganohydrogensilyl groups and forming a silylene structure with the connected silicon atom, when x is 1, B has two or more diorganohydrogensilyl groups, y is 1 or 2, (C) platinum group metal catalyst: 0.1 to 2000 ppm in terms of platinum group metal atoms relative to the mass of component (A); and (D) at least one filler selected from organic resin powder and carbon black powder: 0.1 to 200 parts by mass.

2. The fluoropolyether curable composition according to claim 1, wherein Component (A) is a perfluoropolyether compound represented by the following general formula (2), [Chemistry 2] In the formula, A 1 are independently a divalent organic group having 1 to 20 carbon atoms which may contain at least one selected from an oxygen atom, a nitrogen atom and a silicon atom, 1 is a carbon atom or a silicon atom, X is independently a hydrogen atom, a methyl group or an alkenyl group having 2 to 8 carbon atoms, but at least two X are alkenyl groups having 2 to 8 carbon atoms, and when X is a hydrogen atom, the bonded B 1 is a carbon atom, Rf 1 It is a divalent perfluoropolyether group.

3. The fluoropolyether curable composition according to claim 1, wherein In the component (B), Rf in the general formula (1) is a group represented by the following general formula (5): [Chemistry 3] In the formula, D is a fluorine atom or a perfluorooxyalkyl group having 1 to 6 carbon atoms, a, b, c and d are each independently an integer of 0 to 100, and 2≤a+b+c+d≤100, e is an integer of 1 to 3, and the repeating units shown in the () may be randomly bonded, and these units may be linear or branched.

4. The fluoropolyether curable composition according to claim 1, wherein In the component (B), A in the general formula (1) is selected from: an alkylene group having 1 to 12 carbon atoms, an alkylene group containing an arylene group having 6 to 8 carbon atoms, a divalent group in which alkylene groups are bonded to each other via a diorganosilylene group, a divalent group in which an alkylene group and an arylene group are bonded to each other via a diorganosilylene group, and a divalent group in which these groups further have at least one selected from an ether bond oxygen atom, a secondary amino group, a tertiary amino group and an amide bond.

5. The fluoropolyether curable composition according to claim 1, wherein In the component (B), A in the general formula (1) is any one of the groups represented by the following general formulae (6) to (9), [Chemistry 4] Where, X 0 is a hydrogen atom, a methyl group or an ethyl group, X 1 are independently a hydrogen atom, a fluorine atom, a methyl group, an ethyl group or a trifluoromethyl group, X 2 is a hydrogen atom, a methyl group, an ethyl group, an isopropyl group or a phenyl group, R' is independently a methyl group or an ethyl group, f is an integer of 1 to 6, t is 0 or 1, and the bonding end with * indicates bonding to the Si atom in the general formula (1), and the unmarked bonding end indicates bonding to Rf.

6. The fluoropolyether curable composition according to claim 1, wherein In the component (B), R in the general formula (1) is any one of a methyl group, an ethyl group, an isopropyl group, a tert-butyl group and a phenyl group.

7. The fluoropolyether curable composition according to claim 1, wherein In the component (B), two or more silylene structures are continuous in the molecular chain between Rf in the general formula (1) and the diorganohydrogensilyl group in B.

8. The fluoropolyether curable composition according to claim 1, wherein In the component (B), B in the general formula (1) is a group represented by the following general formula (10), [Chemistry 5] In the formula, p is an integer of 1 to 6, q is an integer of 0 to 6, r is an integer of 1 to 3, R is the same as above, and E is a hydrogen atom or a compound represented by the following formula: [Chemistry 6] A group represented by the formula, wherein R is the same as above, p' is an integer of 1 to 6, q' is an integer of 0 to 6, wherein when E is a hydrogen atom, r is 1, and each repeating unit shown in () with said p, q or p', q' may be randomly bonded.

9. The fluoropolyether curable composition according to claim 1, wherein The component (B) is selected from the group consisting of fluorine-containing organohydrogensilane compounds represented by the following formula: [Chemistry 7] [Chemistry 8] [Chemistry 9] [Chemistry 10] [Chemistry 11] [Chemistry 12] [Chemistry 13] In the formula, b' is an integer of 2 to 100, c' and d' are each an integer of 1 to 99, c'+d'=2 to 100, ca' is an integer of 1 to 99, Me is a methyl group, Et is an ethyl group, Ph is a phenyl group, and the repeating units shown in () with c' and d' may be randomly bonded.

10. The fluoropolyether curable composition according to any one of claims 1 to 9, wherein The average particle size of the component (D) is 0.001 to 100 μm.

11. The fluoropolyether curable composition according to any one of claims 1 to 9, wherein The component (D) is a polyimide resin powder and / or a carbon black powder.

12. The fluoropolyether curable composition according to any one of claims 1 to 9, wherein The component (D) is a pulverized organic resin powder.

13. The fluoropolyether curable composition according to claim 12, wherein The average particle size of the component (D) is 0.001 to 5 μm.

14. The fluoropolyether curable composition according to claim 12, wherein The component (D) is a polyimide resin powder.

15. The fluoropolyether curable composition according to claim 12, wherein The compounding quantity of (D)component is 10-200 mass parts with respect to 100 mass parts of (A)components.

16. A cured product obtained from the fluoropolyether curable composition according to claim 1.

17. An electric or electronic component comprising the cured product according to claim 16.

18. The electric or electronic component according to claim 17, wherein: The cured product is a gasket, filler, protective seal or coating.

19. The electrical and electronic component according to claim 17 or 18, which is used in automobiles, chemical equipment, semiconductor manufacturing lines, analytical physical and chemical equipment, living environments, communication machinery, communication equipment, aircraft, railway vehicles, portable devices, power storage devices, robots, or lithium-ion batteries.

Citation Information

Patent Citations

  • Curable composition

    JP1996199070A

  • Curable composition

    JP1997095615A

  • Curable fluoropolyether rubber composition

    JP2002012769A

  • Fluorine-containing curable composition and rubber product

    JP2011201940A

  • Adhesive composition

    JP2011219692A